Method for manufacturing laminated sheet and method for manufacturing laminate
The method enhances interlayer adhesion in laminated sheets by using a specific isocyanate compound and controlled temperature processes, addressing the challenge of achieving strong adhesion for reinforcement applications.
Patent Information
- Application Number
- JP2023157458
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-03
AI Technical Summary
Existing laminated sheets face challenges in achieving excellent interlayer adhesion between the fiber layer and the resin layer, particularly when used as reinforcement materials in applications such as optical members and vehicle or building window materials.
A method for manufacturing a laminated sheet involving the steps of forming a resin layer using a specific isocyanate compound and a fiber layer with fine fibrous cellulose, followed by controlled drying and heating temperatures to enhance adhesion.
The method results in a laminated sheet with superior interlayer adhesion, allowing for a thicker fiber layer and improved reinforcement functionality.
Smart Images

Figure 2025048575000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a laminate sheet and a method for producing a laminate. [Background technology]
[0002] In recent years, materials using renewable natural fibers have been attracting attention due to the need to replace petroleum resources and growing environmental awareness. Among natural fibers, fibrous cellulose with a fiber width of 10 μm to 50 μm, especially fibrous cellulose (pulp) derived from wood, has been widely used mainly for paper products. As fibrous cellulose, fine fibrous cellulose with a fiber width of 1,000 nm or less is also known. In addition, sheets made of such fine fibrous cellulose, composite sheets containing fine fibrous cellulose and resin, and molded articles have been developed.
[0003] Patent Document 1 describes a laminate sheet having a fiber layer containing fine fibrous cellulose and a resin layer, the laminate sheet having high transparency and suppressed coloration, the laminate sheet having a fiber layer and a resin layer disposed on at least one side of the fiber layer, the fiber layer containing fibrous cellulose having an introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2021-181673 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 describes that the laminate sheet is suitable for applications such as optical components and window materials for various vehicles and buildings. The inventors of the present invention have found that when the laminate sheet is used for the above applications, in order to enhance the function of the laminate sheet as a reinforcing material, it is necessary to thicken the fiber layer, and further, in order to thicken the fiber layer, it is necessary to improve the interlayer adhesion between the fiber layer and the resin layer. An object of the present invention is to provide a method for producing a laminate sheet having excellent interlayer adhesion between a fiber layer and a resin layer, and a method for producing a laminate using the laminate sheet obtained by the method for producing the laminate sheet. [Means for solving the problem]
[0006] The present inventors have discovered that in a method for manufacturing a laminate sheet including steps of forming a fiber layer and a resin layer, the above-mentioned problems can be solved by forming a resin layer using a specific isocyanate compound and controlling the drying or heating temperature in the steps of forming the fiber layer and the resin layer for each step to be lower than or higher than the dissociation temperature of the specific isocyanate compound.
[0007] That is, the present invention provides the following: <1> ~ <15> Regarding. <1> A method for producing a laminate sheet having a resin layer (1A) and a fiber layer in this order on at least one surface of a thermoplastic resin substrate, comprising: The method includes the following steps 1 to 3: Step 1: A step of forming a resin layer (1a) by applying a coating liquid for forming a resin layer (1A) containing a resin and a blocked isocyanate compound to at least one surface of a thermoplastic resin substrate and drying the coating liquid. Step 2: A step of forming a fiber layer by applying a fiber layer-forming coating liquid containing a resin and fine fibrous cellulose having a fiber width of 1 nm or more and 1,000 nm or less to the surface of the resin layer (1a) opposite to the thermoplastic resin substrate, and drying the coating liquid. Step 3: A step of heating the sheet on which the fiber layer is formed to form a resin layer (1A) the drying temperatures in steps 1 and 2 are lower than the dissociation temperature of the blocking agent of the blocked isocyanate compound, and the heating temperature in step 3 is equal to or higher than the dissociation temperature of the blocking agent of the blocked isocyanate compound; A method for manufacturing a laminated sheet. <2> The drying temperature in step 1 is 70°C or higher and 95°C or lower. <1> A method for producing the laminate sheet according to claim 1. <3> The drying temperature in step 2 is 70°C or higher and 100°C or lower. <1> or <2> A method for producing the laminate sheet according to claim 1. <4> The heating temperature in step 3 is 110°C or higher and 130°C or lower. <1> ~ <3> 13. A method for producing the laminate sheet according to claim 12. <5> The thermoplastic resin constituting the thermoplastic resin substrate includes at least one selected from the group consisting of polycarbonate and polyethylene terephthalate; <1> ~ <4> 13. A method for producing the laminate sheet according to claim 12. <6> The coating liquid for forming the resin layer (1A) contains polycarbonate. <1> ~ <5> 13. A method for producing the laminate sheet according to claim 12. <7> The content of fine fibrous cellulose in the solid content of the fiber layer forming coating liquid is 50 mass% or more. <1> ~ <6> 13. A method for producing the laminate sheet according to claim 12. <8> Further, the method includes the following step 4: <1> ~ <7> 13. A method for producing the laminate sheet according to claim 12. Step 4: A step of forming a resin layer (2a) by applying a coating liquid for forming a resin layer (2A) containing a resin and at least one compound selected from the group consisting of an isocyanate compound and a blocked isocyanate compound to the surface of the fiber layer opposite to the resin layer (1A) and drying the coating liquid. <9> The drying temperature in step 4 is 60°C or higher and 85°C or lower. <8> A method for producing the laminate sheet according to claim 1. <10> Further, the method includes the following step 5. <8> or <9> A method for producing the laminate sheet according to claim 1. Step 5: A step of heating the sheet that has been subjected to step 4 to form a resin layer (2A) <11> The heating temperature in step 5 is 80°C or higher and 135°C or lower. <10> A method for producing the laminate sheet according to claim 1. <12> The coating liquid for forming the resin layer (2A) contains polycarbonate. <8> ~ <11> 13. A method for producing the laminate sheet according to claim 12. <13> The resin layer (2a) contains an isocyanate compound. <8> ~ <12> 13. A method for producing the laminate sheet according to claim 12. <14> The blocked isocyanate compound is a compound obtained by blocking the isocyanato group of hexamethylene diisocyanate. <1> ~ <13> 13. A method for producing the laminate sheet according to claim 12. <15> <10> ~ <14> and bonding the resin layer (2A) of the laminate sheet obtained by the method for producing a laminate sheet according to any one of the above to a resin plate. Effect of the Invention
[0008] According to the present invention, there are provided a method for producing a laminate sheet having excellent interlayer adhesion between a fiber layer and a resin layer, and a method for producing a laminate using the laminate sheet obtained by the method for producing the laminate sheet. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view illustrating the configuration of a laminate sheet obtained by a method for producing a laminate sheet according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating the configuration of a laminate sheet obtained by a method for producing a laminate sheet according to another embodiment of the present invention. [Diagram 3] FIG. 3 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxoacid groups and pH. [Figure 4] FIG. 4 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having a carboxy group and pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described. In this specification, "X to Y" indicating a range means "X or more and Y or less". In this specification, the upper and lower limits of the numerical ranges can be combined arbitrarily. In this specification, the components contained in the coating liquid for forming each layer of the laminate sheet (essential components) and the components that can be contained (optional components) can be used alone or in combination of two or more.
[0011] [Manufacturing method of laminated sheet] The method for producing a laminate sheet of the present embodiment is a method for producing a laminate sheet having a resin layer (1A) and a fiber layer in this order on at least one surface of a thermoplastic resin substrate, The method includes the following steps 1 to 3: Step 1: A step of forming a resin layer (1a) by applying a coating liquid for forming a resin layer (1A) containing a resin and a blocked isocyanate compound to at least one surface of a thermoplastic resin substrate and drying the coating liquid. Step 2: A step of forming a fiber layer by applying a fiber layer-forming coating liquid containing a resin and fine fibrous cellulose having a fiber width of 1 nm or more and 1,000 nm or less to the surface of the resin layer (1a) opposite to the thermoplastic resin substrate, and drying the coating liquid. Step 3: A step of heating the sheet on which the fiber layer is formed to form a resin layer (1A) The drying temperatures in steps 1 and 2 are lower than the dissociation temperature of the blocking agent of the blocked isocyanate compound, and the heating temperature in step 3 is equal to or higher than the dissociation temperature of the blocking agent of the blocked isocyanate compound.
[0012] The laminate sheet obtained by the method for producing a laminate sheet according to the present embodiment has excellent interlayer adhesion between the fiber layer and the resin layer, the mechanism of which is presumed to be as follows. Since the drying temperature in steps 1 and 2 is lower than the dissociation temperature of the blocking agent of the blocked isocyanate compound, it is possible to prevent the blocking agent from being dissociated in steps 1 and 2 and being consumed before the isocyanato group reacts with the resin of the fiber layer. Then, by heating at a temperature equal to or higher than the dissociation temperature of the blocking agent in step 3, the blocking agent is dissociated from the isocyanate compound and the isocyanato group can react with the resin in the resin layer (1a) and the fiber layer. Thus, according to the manufacturing method of the laminate sheet of this embodiment, the function of the isocyanate compound as an adhesion assistant can be effectively expressed, which is considered to be one of the reasons for the excellent interlayer adhesion described above. Since the laminate sheet obtained by the manufacturing method of the laminate sheet of this embodiment has excellent interlayer adhesion between the fiber layer and the resin layer, it is considered that the fiber layer can be made thicker than that of a conventional laminate sheet and the function as a reinforcing material can be enhanced. It should be noted that the above mechanism is merely speculation, and the present invention is not limited thereto.
[0013] [Process 1] Step 1 is a step of forming a resin layer (1a) by applying a coating liquid for forming a resin layer (1A) containing a resin and a blocked isocyanate compound to at least one surface of a thermoplastic resin substrate and drying the coating liquid.
[0014] <Thermoplastic resin base material> The thermoplastic resin constituting the thermoplastic resin substrate is not particularly limited, but preferably contains at least one selected from the group consisting of polycarbonate and polyethylene terephthalate, and more preferably contains polycarbonate or polyethylene terephthalate. In the thermoplastic resin constituting the thermoplastic resin substrate, the total content of polycarbonate and polyethylene terephthalate is preferably 85 mass % or more, more preferably 90 mass % or more, and even more preferably 95 mass % or more, and 100 mass % or less.
[0015] <Coating solution for forming resin layer (1A)> The coating liquid for forming the resin layer (1A) contains a resin and a blocked isocyanate compound.
[0016] (resin) From the viewpoint of improving the interlayer adhesion between the fiber layer and the resin layer, the resin is preferably polycarbonate, acrylic resin, polyurethane, polyester, or epoxy resin, and more preferably polycarbonate. The content of polycarbonate in the resin is preferably 85% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and 100% by mass or less, preferably 100% by mass. In this specification, "polycarbonate" means a resin containing a site in which structural units are repeatedly bonded via a carbonate group (-O-(C=O)-O-).
[0017] (Blocked isocyanate compound) The term "blocked isocyanate compound" refers to a compound having a structure in which the isocyanato group of a polyisocyanate compound is protected with a blocking agent. The dissociation temperature of the blocking agent is not particularly limited as long as it is higher than the drying temperature in steps 1 and 2 and lower than the heating temperature in step 3, and is, for example, 110°C or higher and 130°C or lower. The dissociation temperature of the blocking agent refers to the "temperature of the endothermic peak associated with the deprotection reaction of the blocked isocyanate compound when measured by DSC (Differential Scanning Calorimetry) analysis using a differential scanning calorimeter." An example of a differential scanning calorimeter is a differential scanning calorimeter (NEXTA STA200) manufactured by Hitachi High-Tech Corporation.
[0018] Examples of blocking agents having a dissociation temperature of 110° C. or higher and 130° C. or lower include amine-based blocking agents (amine compounds), oxime-based blocking agents (compounds having “>C═N—OH”), and phenol-based blocking agents (phenol compounds) to which a tin catalyst has been added. Amine-based blocking agents include, for example, diphenylamine, aniline, and propylamine. An example of an oxime-based blocking agent is methyl ethyl ketone oxime. Phenolic blocking agents include, for example, cresol and phenol.
[0019] Examples of the blocked isocyanate compound used in the method for producing the laminate sheet of the present embodiment include compounds in which the isocyanate compound described below is protected with the above-mentioned blocking agent. As the isocyanate compound, an aliphatic polyisocyanate having 2 to 18 carbon atoms is preferable, and hexamethylene diisocyanate is more preferable.
[0020] The blocked isocyanate compound may be a commercially available product. An example of an isocyanate compound blocked with an amine-based blocking agent is Takenate XB-G206 (manufactured by Mitsui Chemicals, Inc.). An example of an isocyanate compound blocked with an oxime-based blocking agent is Takenate B-882N (manufactured by Mitsui Chemicals, Inc.). An example of an isocyanate compound blocked with a phenol-based blocking agent is Bronate 1902 (manufactured by Daiei Sangyo Co., Ltd.).
[0021] In the method for producing a laminate sheet of this embodiment, for example, an isocyanate compound blocked with a blocking agent having a dissociation temperature of less than 110° C. can be used in accordance with the drying temperatures in steps 1 and 2 and the heating temperature in step 3. Examples of isocyanate compounds blocked with a blocking agent having a dissociation temperature of less than 110° C. include isocyanate compounds blocked with an active methylene blocking agent (active methylene compound), and specific examples of such isocyanate compounds include Bronate 1227EV and Bronate 1232EV (manufactured by Daiei Sangyo Co., Ltd.).
[0022] (Organic solvent) From the viewpoint of ease of forming the resin layer (1a), the coating liquid for forming the resin layer (1A) preferably contains an organic solvent. Examples of the organic solvent include toluene, methylene chloride, tetrahydrofuran, tetraglyme, dimethyl carbonate, methyl ethyl ketone, ethyl acetate, and dimethylacetamide, with toluene being preferred.
[0023] (Other Ingredients 1) The coating liquid for forming the resin layer (1A) may contain components other than the above-mentioned resin, blocked isocyanate compound, and organic solvent ("other components 1"). Examples of other components 1 include known components used in the field of resin films, such as fillers, pigments, dyes, and ultraviolet absorbers.
[0024] (Content) The solid content of the coating liquid for forming the resin layer (1A) is, from the viewpoints of easiness in forming the resin layer (1a) and improving the interlayer adhesion between the fiber layer and the resin layer, preferably 3 mass % or more, more preferably 6 mass % or more, even more preferably 9 mass % or more, and is preferably 30 mass % or less, more preferably 25 mass % or less, even more preferably 20 mass % or less. The resin content in the solid content of the coating liquid for forming the resin layer (1A) is, from the viewpoints of easiness in forming the resin layer (1a) and improving the interlayer adhesion between the fiber layer and the resin layer, preferably 40 mass% or more, more preferably 50 mass% or more, even more preferably 60 mass% or more, and is preferably 90 mass% or less, more preferably 85 mass% or less, even more preferably 80 mass% or less. The content of the blocked isocyanate compound in the solids contained in the coating liquid for forming the resin layer (1A) is, from the viewpoints of easiness in forming the resin layer (1a) and improvement in interlayer adhesion between the fiber layer and the resin layer, preferably 10 mass % or more, more preferably 15 mass % or more, even more preferably 20 mass % or more, and is preferably 50 mass % or less, more preferably 45 mass % or less, even more preferably 40 mass % or less. From the viewpoint of improving the interlayer adhesion between the fiber layer and the resin layer, the total content of the resin and the blocked isocyanate compound in the solid content of the coating liquid for forming the resin layer (1A) is preferably 85 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and 100 mass% or less, preferably 100 mass%. In the coating liquid for forming the resin layer (1A), the content of the blocked isocyanate compound relative to 100 parts by mass of the resin is, from the viewpoint of improving the interlayer adhesion between the fiber layer and the resin layer, preferably 20 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 40 parts by mass or more, and is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less. In the solid content of the coating liquid for forming the resin layer (1A), the content of other component 1 is preferably 5 mass% or less, more preferably 3 mass% or less, even more preferably 1 mass% or less, and is 0 mass% or more, preferably 0 mass%.
[0025] (concentration) The solid content concentration in the coating liquid for forming the resin layer (1A) is, from the viewpoint of forming a resin layer (1a) in which the solid content in the coating liquid is uniformly dispersed, preferably 1 mass % or more, more preferably 5 mass % or more, even more preferably 10 mass % or more, and is preferably 40 mass % or less, more preferably 30 mass % or less, even more preferably 20 mass % or less.
[0026] (Coating and drying) The coating liquid for forming the resin layer (1A) can be applied to the thermoplastic resin substrate using a known coater, such as a bar coater, roll coater, gravure coater, die coater, curtain coater, air doctor coater, etc. The drying temperature is not limited as long as the resin layer (1a) can be formed at a temperature lower than the dissociation temperature of the blocking agent of the blocked isocyanate compound, and is preferably at least 70° C., more preferably at least 75° C., and is preferably at most 95° C., more preferably at most 90° C. The drying time is, for example, preferably at least 1 minute, more preferably at least 2 minutes, and is preferably at most 20 minutes, more preferably at most 10 minutes.
[0027] The drying method is not particularly limited, and may be either a non-contact drying method or a method in which the sheet consisting of the thermoplastic resin substrate and the resin layer (1a) is dried while being restrained, or a combination of these may be used. The non-contact drying method is not particularly limited, but may be a method of drying by heating with hot air, infrared rays, far infrared rays or near infrared rays (heat drying method), or a method of drying by vacuum (vacuum drying method). The heat drying method and the vacuum drying method may be combined, but the heat drying method is usually applied. Drying by infrared rays, far infrared rays or near infrared rays may be performed using an infrared device, a far infrared device or a near infrared device, but is not particularly limited.
[0028] [Process 2] Step 2 is a step of forming a fiber layer by coating and drying a coating liquid for forming a fiber layer, the coating liquid containing a resin and fine fibrous cellulose having a fiber width of 1 nm or more and 1,000 nm or less, on the surface of the resin layer (1a) opposite the thermoplastic resin substrate.
[0029] (resin) From the viewpoint of ease of manufacturing the fiber layer, the resin contained in the fiber layer forming coating liquid is preferably a hydrophilic polymer. A hydrophilic polymer is generally a polymeric compound that is easily dissolved, swollen, or wetted by water. Examples of the hydrophilic polymer include a polymeric compound having an ionic group such as a carboxy group, a sulfone group, or an amino group in the molecular structure, and a polymeric compound having a non-ionic hydrophilic group such as a hydroxyl group, an amide group, an ether group, or a polyoxyethylene group or a polyoxypropylene group. Hydrophilic polymers include carboxyvinyl polymers, polyvinyl alcohol, alkyl methacrylate-acrylic acid copolymers, polyvinylpyrrolidone, polyvinyl methyl ether, polyacrylates such as sodium polyacrylate, alkyl acrylate copolymers, urethane copolymers, modified polyesters, modified polyimides, polyalkylene glycols such as polyethylene glycol and polypropylene glycol, polycations such as polyacrylamide and polyethyleneimine, polyanions, amphoteric polymers, xanthan gum, guar gum, tamarind gum, carrageenan, locust bean gum, quince seed, and a Examples of the thickening polysaccharides include alginic acid, metal salts of alginic acid, pullulan, sacran, and pectin; cellulose derivatives include carboxymethylcellulose, carboxyethylcellulose, methylcellulose, hydroxypropylmethylcellulose, hydroxyethylmethylcellulose, and hydroxyethylcellulose; starches include cationic starch, raw starch, oxidized starch, etherified starch, esterified starch, dextrin, and amylose; glycerins such as polyglycerin; hyaluronic acid, metal salts of hyaluronic acid; and proteins such as casein.Also, it may be a copolymer of these hydrophilic polymers. Among these, polyvinyl alcohol, polyethyleneimine, and cellulose derivatives are preferred, cellulose derivatives are more preferred, and hydroxypropylmethylcellulose is even more preferred.
[0030] (Fine fibrous cellulose) Fine fibrous cellulose is fibrous cellulose with a fiber width of 1 nm or more and 1,000 nm or less. Hereinafter, fibrous cellulose with a fiber width of 1 nm or more and 1,000 nm or less may be simply referred to as "fine fibrous cellulose" or "fibrous cellulose." The fiber width of fibrous cellulose can be measured, for example, by observation using an electron microscope. The fiber width of the fine fibrous cellulose is 1 nm or more and 1,000 nm or less. The fiber width of the fine fibrous cellulose is, for example, preferably 2 nm or more and 1,000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. By making the fiber width of the fine fibrous cellulose 2 nm or more, it is possible to suppress dissolution of the cellulose molecules in water, and to more easily realize the effect of improving the strength, rigidity, and dimensional stability of the fine fibrous cellulose.
[0031] The average fiber width of the fine fibrous cellulose is, for example, 1 nm or more and 1,000 nm or less. The average fiber width of the fine fibrous cellulose is preferably 2 nm or more and 1,000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. By making the average fiber width of the fine fibrous cellulose 2 nm or more, it is possible to suppress dissolution of the cellulose molecules in water, and to more easily realize the effect of improving the strength, rigidity, and dimensional stability of the fine fibrous cellulose. The fine fibrous cellulose is, for example, a single-fiber cellulose.
[0032] The number-average fiber width of fine fibrous cellulose is measured, for example, using an electron microscope as follows. First, an aqueous suspension of fibrous cellulose with a concentration of 0.01% by mass or more and 0.1% by mass or less is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for observation with a transmission electron microscope (TEM). When wide fibers are included, a scanning electron microscope (SEM) image of the surface cast on glass may be observed. Next, observation is performed using an electron microscope image at a magnification of 1,000x, 5,000x, 10,000x, or 50,000x depending on the width of the fiber to be observed. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions. (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y.
[0033] For observation images that satisfy the above conditions, the width of the fibers that intersect with lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers that intersect with lines X and Y is read. In this manner, the width of at least 20 fibers x 2 x 3 = 120 fibers is read. The average value of the read fiber widths is then determined as the average fiber width of the fibrous cellulose.
[0034] The fiber length of the fine fibrous cellulose is not particularly limited, but is preferably, for example, 0.1 μm to 1,000 μm, more preferably 0.1 μm to 800 μm, and even more preferably 0.1 μm to 600 μm. By setting the fiber length within the above range, destruction of the crystalline region of the fine fibrous cellulose can be suppressed. It is also possible to set the slurry viscosity of the fine fibrous cellulose to an appropriate range. The fiber length of the fine fibrous cellulose can be determined by image analysis using, for example, TEM, SEM, or atomic force microscope (AFM).
[0035] The fine fibrous cellulose preferably has a type I crystal structure. The fact that the fine fibrous cellulose has a type I crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromated with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. This is expected to provide even better performance in terms of low linear thermal expansion coefficient. The degree of crystallinity is determined by measuring an X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0036] The axial ratio (fiber length / fiber width) of the fine fibrous cellulose is not particularly limited, but is preferably, for example, 20 to 10,000, and more preferably 50 to 1,000. By setting the axial ratio to the above lower limit or more, a sheet containing the fine fibrous cellulose can be easily formed. By setting the axial ratio to the above upper limit or less, it is preferable in that, for example, when the fine fibrous cellulose is treated as an aqueous dispersion, handling such as dilution is facilitated.
[0037] In the present embodiment, the fine fibrous cellulose preferably has at least one of an ionic substituent and a nonionic substituent. From the viewpoint of improving the dispersibility of the fibers in the dispersion medium and increasing the defibration efficiency in the defibration treatment step, it is more preferable that the fine fibrous cellulose has an ionic substituent. The ionic substituent may include, for example, either one or both of an anionic group and a cationic group. Furthermore, the nonionic substituent may include, for example, an alkyl group and an acyl group. In the present embodiment, it is particularly preferable that the ionic substituent has an anionic group. Furthermore, the ionic substituent is preferably a group that is introduced into the fine fibrous cellulose via an ester bond or an ether bond, and more preferably a group that is introduced into the fine fibrous cellulose via an ester bond. In this case, the ester bond is preferably formed by dehydration condensation of the fine fibrous cellulose and a compound that becomes an ionic substituent. The fine fibrous cellulose does not necessarily need to be subjected to a treatment for introducing an ionic substituent.
[0038] Examples of anionic groups as ionic substituents include phosphorus oxoacid groups or substituents derived from phosphorus oxoacid groups (sometimes simply referred to as phosphorus oxoacid groups), carboxy groups or substituents derived from carboxy groups (sometimes simply referred to as carboxy groups), sulfur oxoacid groups or substituents derived from sulfur oxoacid groups (sometimes simply referred to as sulfur oxoacid groups), xanthate groups or substituents derived from xanthate groups (sometimes simply referred to as xanthate groups), phosphonic groups or substituents derived from phosphonic groups, phosphine groups or substituents derived from phosphine groups, sulfone groups or substituents derived from sulfone groups, and carboxyalkyl groups. Among them, the anionic group is preferably at least one selected from the group consisting of phosphorus oxo acid group, substituents derived from phosphorus oxo acid group, carboxy group, carboxymethyl group, carboxyethyl group, sulfur oxo acid group and sulfur oxo acid group, xanthate group, and substituents derived from sulfone group, more preferably at least one selected from the group consisting of phosphorus oxo acid group, substituents derived from phosphorus oxo acid group, carboxy group, sulfur oxo acid group, substituents derived from sulfur oxo acid group, and xanthate group, more preferably at least one selected from the group consisting of phosphorus oxo acid group, substituents derived from phosphorus oxo acid group, carboxy group, sulfur oxo acid group, and substituents derived from sulfur oxo acid group, and particularly preferably phosphorus oxo acid group. By introducing a phosphorus oxo acid group as an anionic group, for example, even under alkaline conditions or acidic conditions, the dispersibility of fibrous cellulose can be further increased, and as a result, a high-strength and highly transparent fine fibrous cellulose-containing layer is easily obtained. Examples of the cationic group as the ionic substituent include an ammonium group, a phosphonium group, a sulfonium group, etc. Among these, the cationic group is preferably an ammonium group.
[0039] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). A plurality of substituents represented by the following formula (1) may be introduced into each fine fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (1) may be the same or different.
[0040] [ka]
[0041] In formula (1), a, b, and n are natural numbers, and m is an arbitrary number (where a=b×m). At least one of n α and α′ (preferably a) is O. - and the rest are R or OR. Note that each α and α' is O. - The n α's may all be the same or may be different. b+ is a cation of one or more valences consisting of organic or inorganic substances. Each R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In addition, α in formula (1) may be a group derived from a cellulose molecular chain. In addition, in formula (1), n is preferably 1.
[0042] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups. In addition, the derivative group in R is a carboxy group, a carboxylate group (-COO - ), a hydroxy group, an amino group, and other functional groups may be added or substituted with at least one functional group, but is not particularly limited thereto. The number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, and more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set within an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fine fibrous cellulose. When multiple Rs are present in formula (1) or multiple types of substituents represented by the above formula (1) are introduced into the fine fibrous cellulose, the multiple Rs may be the same or different.
[0043] β b+is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic phosphonium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic phosphonium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is, but is not limited to, an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. These may be used alone or in combination of two or more kinds. In addition, β in formula (1) b+ When a plurality of β b+ may be the same or different. The organic or inorganic cations of monovalent or higher include β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0044] More specifically, examples of the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group include a phosphate group (-PO3H2), a salt of a phosphate group, a phosphorous acid group (phosphonic acid group) (-PO2H2), and a salt of a phosphite group (phosphonic acid group). The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group may be a group in which a phosphate group is condensed (e.g., a pyrophosphate group), a group in which a phosphonic acid is condensed (e.g., a polyphosphonic acid group), a phosphate ester group (e.g., a monomethyl phosphate group, a polyoxyethylene alkyl phosphate group), an alkyl phosphonic acid group (e.g., a methyl phosphonic acid group), and the like.
[0045] The sulfur oxoacid group (sulfur oxoacid group or a substituent derived from a sulfur oxoacid group) is, for example, a substituent represented by the following formula (2). A plurality of types of substituents represented by the following formula (2) may be introduced into each fine fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (2) may be the same or different.
[0046] [ka]
[0047] In formula (2), b and n are natural numbers, p is 0 or 1, and m is an arbitrary number (where 1=b×m). When n is 2 or more, the multiple p's may be the same or different numbers. In formula (2), β b+ is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic phosphonium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic phosphonium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. When multiple types of substituents represented by the above formula (2) are introduced into the fine fibrous cellulose, the multiple β b+ may be the same or different. The organic or inorganic cations of monovalent or higher include β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0048] The amount of ionic substituent introduced into the fine fibrous cellulose is preferably 0.05 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of ionic substituent introduced into the fine fibrous cellulose is preferably 5.20 mmol / g or less per 1 g (mass) of fibrous cellulose, more preferably 3.65 mmol / g or less, even more preferably 3.50 mmol / g or less, and even more preferably 3.00 mmol / g or less. By setting the amount of ionic substituent (preferably anionic group) introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fine fibrous cellulose. Here, the denominator in the unit mmol / g is the counter ion of the ionic substituent, which is a hydrogen ion (H + ) indicates the mass of the fine fibrous cellulose when
[0049] In addition, the amount of ionic substituents (preferably anionic groups) introduced into the fine fibrous cellulose is preferably less than 0.50 mmol / g per 1 g (mass) of fine fibrous cellulose from the viewpoint of reducing the water absorption and yellow index of the laminated sheet, more preferably 0.40 mmol / g or less, even more preferably 0.30 mmol / g or less, even more preferably 0.25 mmol / g or less, and particularly preferably 0.15 mmol / g or less, and from the viewpoint of the haze of the laminated sheet, is preferably 0.01 mmol / g or more, more preferably 0.02 mmol / g or more, and even more preferably 0.03 mmol / g or more. Such a low-substituent amount fine fibrous cellulose may be obtained, for example, by subjecting the fine fibrous cellulose after the defibration treatment to a treatment for removing the substituents from the fine fibrous cellulose, which will be described later. In the coating liquid for forming the fiber layer, it is preferable to use the above-mentioned low-substituent amount fine fibrous cellulose from the viewpoint of the transparency of the laminated sheet.
[0050] The amount of ionic substituent introduced into the fine fibrous cellulose can be measured, for example, by neutralization titration. In the measurement by neutralization titration, an alkali such as an aqueous sodium hydroxide solution is added to the obtained slurry containing the fine fibrous cellulose, and the amount introduced is measured by determining the change in pH.
[0051] 3 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxo acid groups and pH. The amount of phosphorus oxo acid groups introduced into the fibrous cellulose is measured, for example, as follows. First, a slurry containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, the measurement target may be subjected to a defibration treatment similar to the defibration treatment step described below prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 3 is obtained. In the titration curve shown in the upper part of Figure 3, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 3, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH against the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total amount of dissociated acid of the fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxo acid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxo acid group introduced (or the amount of phosphorus oxo acid group), it refers to the amount of the first dissociated acid. In FIG. 3, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups in the phosphorus oxoacid group (also referred to as the second dissociated acid amount in this specification) appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups in the phosphorus oxoacid group (also referred to as the first dissociated acid amount in this specification) is equal to the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphorous acid group, the phosphorus oxoacid group no longer has weak acid groups, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum. The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups possessed by the acid-type fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with an arbitrary cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups possessed by the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Amount of phosphorus oxoacid group (C type) = Amount of phosphorus oxoacid group (acid type) / {1+(W-1)×A / 1000} A [mmol / g]: total amount of anions derived from phosphorus oxoacid groups in fibrous cellulose (sum of the amount of strong acidic groups and weak acidic groups in phosphorus oxoacid groups) W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0052] FIG. 4 is a graph showing the relationship between the amount of NaOH dropped onto the fine fibrous cellulose having a carboxy group and the pH. The amount of carboxyl groups introduced into the fine fibrous cellulose is measured, for example, as follows. First, a slurry containing fine fibrous cellulose is treated with a strong acid ion exchange resin. If necessary, the measurement object may be subjected to a defibration treatment similar to the defibration treatment process described below before the treatment with the strong acid ion exchange resin. Next, the change in pH is observed while adding an aqueous sodium hydroxide solution, and a titration curve as shown in FIG. 4 is obtained. If necessary, the measurement object may be subjected to a defibration treatment similar to the defibration treatment process described below. As shown in FIG. 4, in this neutralization titration, a single point is observed where the increment (the derivative of pH with respect to the amount of alkali added) is maximum on the curve plotting the measured pH against the amount of alkali added. This maximum point of the increment is called the first end point. Here, the region from the start of the titration to the first end point in FIG. 4 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the slurry used in the titration. The amount of alkali introduced (mmol / g) was calculated by dividing the amount of alkali required in the first region of the titration curve (mmol) by the solid content (g) in the fine fibrous cellulose-containing slurry to be titrated. The amount of carboxyl groups introduced (mmol / g) is calculated assuming that the counter ion of the carboxyl group is a hydrogen ion (H + ) (hereinafter referred to as the amount of carboxy groups (acid type)) per gram of mass of fibrous cellulose.
[0053] The above-mentioned amount of carboxyl groups introduced (mmol / g) indicates the amount of carboxyl groups in the acid-type fibrous cellulose (hereinafter referred to as the amount of carboxyl groups (acid type)) since the denominator is the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the carboxyl group is replaced with any cation C so as to be the charge equivalent, the amount of carboxyl groups in the fibrous cellulose with the cation C as the counter ion (hereinafter referred to as the amount of carboxyl groups (C type)) (mmol / g) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Carboxylic acid amount (C type) = Carboxylic acid amount (acid type) / {1 + (W-1) x (Carboxylic acid amount (acid type)) / 1000} W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0054] In measuring the amount of substituents by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of substituents may be lower than the actual amount, and an accurate value may not be obtained. For example, it is preferable to titrate 10 to 50 μL of 0.1N sodium hydroxide solution every 5 to 30 seconds as an appropriate amount of dropping and titration interval. In addition, in order to eliminate the influence of carbon dioxide dissolved in the fibrous cellulose-containing slurry, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.
[0055] The amount of sulfur oxoacid groups or sulfone groups introduced into fibrous cellulose can be calculated by freeze-drying a slurry containing fibrous cellulose, pulverizing the slurry, and measuring the amount of sulfur in the resulting pulverized sample. Specifically, a slurry containing fibrous cellulose is freeze-dried, and the resulting pulverized sample is subjected to pressurized heating decomposition with nitric acid in a closed container, and then appropriately diluted and the amount of sulfur is measured by ICP-OES. The amount of sulfur oxoacid groups or sulfone groups (unit: mmol / g) of fibrous cellulose is calculated by dividing the value by the bone dry mass of the fibrous cellulose used.
[0056] <<Method of producing fine fibrous cellulose>> (cellulose-containing fiber materials) Fine fibrous cellulose is produced from a fiber raw material containing cellulose. The fiber raw material containing cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not particularly limited to, chemical pulp such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP), and oxygen bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), and mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP). Examples of non-wood pulp include, but are not particularly limited to, cotton-based pulp such as cotton linters and cotton lint, and non-wood-based pulp such as hemp, wheat straw, and bagasse. The deinked pulp is not particularly limited, but may be, for example, deinked pulp made from recycled paper. The pulp of this embodiment may be one of the above types alone or a mixture of two or more types. Among the above pulps, for example, wood pulp and deinked pulp are preferred from the viewpoint of availability. Furthermore, among wood pulps, for example, chemical pulp is more preferred, and kraft pulp and sulfite pulp are even more preferred, from the viewpoint of a high cellulose ratio and a high yield of fine fibrous cellulose during defibration treatment, and of obtaining long-fiber fine fibrous cellulose with a large axial ratio due to little decomposition of cellulose in the pulp. Note that the viscosity tends to increase when long-fiber fine fibrous cellulose with a large axial ratio is used. As a fiber raw material containing cellulose, for example, cellulose contained in sea squirts and bacterial cellulose produced by acetic acid bacteria can be used. Moreover, instead of fiber raw materials containing cellulose, fibers formed from linear nitrogen-containing polysaccharide polymers such as chitin and chitosan can also be used.
[0057] In order to obtain the fine fibrous cellulose having the ionic substituent introduced therein, it is preferable to have an ionic substituent introduction step for introducing an ionic substituent into the fiber raw material containing the above-mentioned cellulose, a washing step, an alkali treatment step (neutralization step), and a defibration treatment step in this order, and an acid treatment step may be included instead of or in addition to the washing step. Examples of the ionic substituent introduction step include a phosphorus oxo acid group introduction step, a carboxy group introduction step, a sulfur oxo acid group introduction step, a xanthate group introduction step, a phosphonic or phosphine group introduction step, a sulfonic group introduction step, and a cationic group introduction step. Each of these steps will be described below.
[0058] (Ionic Substituent Introduction Step) -Phosphorus oxo acid group introduction process- The phosphorus oxo acid group introduction step is a step in which at least one compound selected from compounds capable of introducing phosphorus oxo acid groups by reacting with hydroxyl groups in a fiber raw material containing cellulose (hereinafter also referred to as "compound A") is allowed to act on the fiber raw material containing cellulose, thereby obtaining a fiber into which phosphorus oxo acid groups have been introduced. In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B"). Alternatively, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the absence of compound B. An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, because of its high reactivity. The form of the fiber raw material is not particularly limited, but it is preferable to use a cotton-like or thin sheet-like form, for example. Compound A and compound B can be added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, because the reaction is highly uniform. In addition, compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution form, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.
[0059] The compound A used in this embodiment may be any compound that has a phosphorus atom and can form an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be, for example, 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and may include, for example, pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates may include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high efficiency of introduction of phosphorus oxoacid groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, and ammonium dihydrogen phosphate are more preferred. The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to 100 parts by mass of the fiber raw material (bone dry mass) is preferably 0.5 parts by mass or more and 100 parts by mass or less, more preferably 1 part by mass or more and 50 parts by mass or less, and even more preferably 2 parts by mass or more and 30 parts by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance between the effect of improving the yield and the cost can be achieved.
[0060] As described above, the compound B used in this embodiment is at least one selected from urea and its derivatives. Examples of the compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use an aqueous solution of compound B. Also, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved. The amount of compound B added per 100 parts by mass (bone dry mass) of the fiber raw material is not particularly limited, but is preferably, for example, 1 part by mass or more and 500 parts by mass or less, more preferably 10 parts by mass or more and 400 parts by mass or less, and even more preferably 100 parts by mass or more and 350 parts by mass or less.
[0061] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.
[0062] In the phosphorus oxo acid group introduction step, it is preferable to add or mix the compound A or the like to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that can efficiently introduce the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C to 300°C, more preferably 100°C to 250°C, and even more preferably 130°C to 200°C. In addition, for the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, and a high-frequency dryer.
[0063] In the heat treatment according to the present embodiment, for example, a method of adding compound A to a thin sheet-like fiber raw material by a method such as impregnation and then heating, or a method of heating while kneading or stirring the fiber raw material and compound A in a kneader or the like can be adopted. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and introduce phosphorus oxoacid groups more uniformly onto the surface of the cellulose fibers contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A can be prevented from being attracted to the water molecules by surface tension and moving to the surface of the fiber raw material in the same manner (i.e., causing unevenness in the concentration of compound A). In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, to the outside of the device system, the moisture held by the slurry and the moisture generated by the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio. The time for the heat treatment is, for example, preferably from 1 second to 300 minutes after the moisture is substantially removed from the fiber raw material, more preferably from 1 second to 1,000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.
[0064] The amount of phosphorus oxoacid groups introduced into the fiber raw material is preferably 0.05 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of phosphorus oxoacid groups introduced into the fiber raw material is preferably 5.20 mmol / g or less per 1 g (mass) of fine fibrous cellulose, more preferably 3.65 mmol / g or less, and even more preferably 3.00 mmol / g or less. By setting the amount of phosphorus oxoacid groups introduced within the above range, it is possible to easily fine the fiber raw material and to increase the stability of the fine fibrous cellulose.
[0065] -Carboxy group introduction process- The carboxyl group introduction process is carried out by subjecting a fiber raw material containing cellulose to an oxidation process such as ozone oxidation, oxidation by the Fenton method, or TEMPO oxidation treatment, or by treating the raw material with a compound having a carboxylic acid-derived group or a derivative thereof, or an acid anhydride or a derivative thereof of a compound having a carboxylic acid-derived group. Examples of compounds having a group derived from a carboxylic acid include, but are not limited to, dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Examples of derivatives of compounds having a group derived from a carboxylic acid include, but are not limited to, imidized products of acid anhydrides of compounds having a carboxy group, and derivatives of acid anhydrides of compounds having a carboxy group. Examples of imidized products of acid anhydrides of compounds having a carboxy group include, but are not limited to, imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.
[0066] The acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, etc. Furthermore, the derivative of an acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of compounds having a carboxy group such as dimethylmaleic anhydride, diethylmaleic anhydride, diphenylmaleic anhydride, etc., in which at least a part of the hydrogen atoms is substituted with a substituent such as an alkyl group or a phenyl group.
[0067] When a TEMPO oxidation treatment is performed in the carboxyl group introduction step, it is preferable to perform the treatment under conditions of a pH of 6 or more and 8 or less. Such a treatment is also called a neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be performed, for example, by adding pulp as a fiber raw material, a nitroxy radical such as TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). Furthermore, by adding sodium chlorite, the aldehyde generated during the oxidation process can be efficiently oxidized to a carboxyl group. The TEMPO oxidation treatment may be carried out under conditions of a pH of 10 to 11. This type of treatment is also called alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be carried out, for example, by adding a nitroxy radical such as TEMPO as a catalyst, sodium bromide as a co-catalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material. The amount of carboxyl groups introduced into the fiber raw material varies depending on the type of the substituent, but for example, when the carboxyl groups are introduced by TEMPO oxidation, it is preferably 0.05 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 0.90 mmol / g or more. Also, it is preferably 3.65 mmol / g or less, more preferably 3.00 mmol / g or less, even more preferably 2.50 mmol / g or less, even more preferably 2.20 mmol / g or less, and particularly preferably 2.00 mmol / g or less. In addition, when the substituent is a carboxymethyl group, it may be 5.8 mmol / g or less per 1 g (mass) of fine fibrous cellulose. By setting the amount of carboxyl groups introduced within the above range, it is possible to facilitate the fine pulverization of cellulose fibers in the fine pulverization treatment step and to increase the stability of the fine fibrous cellulose.
[0068] -Sulfur oxo acid group introduction process- The process for producing fine fibrous cellulose may include, for example, a sulfur oxoacid group introduction step as an ionic substituent introduction step, in which a hydroxyl group in a fiber raw material containing cellulose reacts with a sulfur oxoacid to obtain cellulose fibers having sulfur oxoacid groups (sulfur oxoacid group-introduced fibers).
[0069] In the sulfur oxo acid group introduction step, instead of compound A in the above-mentioned <phosphorus oxo acid group introduction step>, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing sulfur oxo acid groups by reacting with hydroxyl groups of fiber raw materials containing cellulose is used. Compound C may be any compound having a sulfur atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, sulfuric acid or a salt thereof, sulfurous acid or a salt thereof, and sulfuric acid amide. As sulfuric acid, sulfuric acid of various purities may be used, for example, 96% sulfuric acid (concentrated sulfuric acid). As sulfurous acid, 5% sulfurous acid water may be used. As sulfates or sulfites, lithium salts, sodium salts, potassium salts, ammonium salts of sulfates or sulfites may be used, and these may be neutralized to various degrees. As sulfuric acid amides, sulfamic acid or the like may be used. In the sulfur oxo acid group introduction step, it is preferable to use compound B in the above-mentioned <phosphorus oxo acid group introduction step> in the same manner.
[0070] In the sulfur oxoacid group introduction step, it is preferable to mix the cellulose raw material with an aqueous solution containing sulfur oxoacid and urea and / or a urea derivative, and then heat-treat the cellulose raw material. It is preferable to select a heat-treating temperature that allows efficient introduction of sulfur oxoacid groups while suppressing thermal decomposition and hydrolysis of the fibers. The heat-treating temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher. The heat-treating temperature is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower.
[0071] In the heat treatment step, it is preferable to heat until substantially no moisture is present. For this reason, the heat treatment time varies depending on the amount of moisture contained in the cellulose raw material and the amount of the aqueous solution containing sulfur oxoacid and urea and / or a urea derivative added, but is preferably, for example, 10 seconds or more and 10,000 seconds or less. For the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, and a high-frequency dryer.
[0072] The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 0.05 mmol / g or more, more preferably 0.10 mmol / g or more, even more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 0.90 mmol / g or more. The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 5.00 mmol / g or less, more preferably 3.00 mmol / g or less. By setting the amount of sulfur oxoacid groups introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fibrous cellulose.
[0073] -Oxidation process using a chlorine-based oxidizing agent (second carboxyl group introduction process)- The ionic substituent introduction step may include an oxidation step using a chlorine-based oxidizing agent, in which the chlorine-based oxidizing agent is added to a wet or dry fiber raw material having a hydroxyl group to cause a reaction, thereby introducing a carboxyl group into the fiber raw material.
[0074] Examples of chlorine-based oxidizing agents include hypochlorous acid, hypochlorites, chlorous acid, chlorites, chloric acid, chlorates, perchloric acid, perchlorates, and chlorine dioxide. In terms of the efficiency of introducing a substituent, and therefore the efficiency of defibration, cost, and ease of handling, the chlorine-based oxidizing agent is preferably sodium hypochlorite, sodium chlorite, or chlorine dioxide. When adding a chlorine-based oxidizing agent, it may be added to the fiber raw material as it is as a reagent (solid or liquid), or it may be added after dissolving in an appropriate solvent.
[0075] The concentration of the chlorine-based oxidizing agent in the solution in the oxidation step using the chlorine-based oxidizing agent is, for example, preferably 1% by mass to 1,000% by mass, more preferably 5% by mass to 500% by mass, and even more preferably 10% by mass to 100% by mass. The amount of the chlorine-based oxidizing agent added per 100 parts by mass of the fiber raw material is preferably 1 part by mass to 100,000 parts by mass, more preferably 10 parts by mass to 10,000 parts by mass, and even more preferably 100 parts by mass to 5,000 parts by mass.
[0076] The reaction time with the chlorine-based oxidizing agent in the oxidation step using the chlorine-based oxidizing agent may vary depending on the reaction temperature, but is preferably from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. The pH during the reaction is preferably from 5 to 15, more preferably from 7 to 14, and even more preferably from 9 to 13. At the start of the reaction, the pH during the reaction is preferably kept constant (for example, pH 11) by appropriately adding hydrochloric acid or sodium hydroxide. After the reaction, excess reaction reagents, by-products, etc. may be washed with water and removed by filtration or the like.
[0077] -Xanthate group introduction process (xanthogen acid esterification process)- The ionic substituent introduction step may include, for example, a xanthate group introduction step (hereinafter also referred to as a xanthate formation step). In the xanthate formation step, carbon disulfide and an alkali compound are added to a wet or dry fiber raw material having a hydroxyl group to react with each other, thereby introducing a xanthate group into the fiber raw material. Specifically, carbon disulfide is added to a fiber raw material that has been converted into alkali cellulose by the method described below, and the reaction is carried out.
[0078] ((Alkaline cellulose)) When introducing an ionic substituent into a fiber raw material, it is preferable to make the cellulose contained in the fiber raw material into an alkali cellulose by applying an alkali solution to the cellulose. This treatment causes some of the hydroxyl groups of the cellulose to be ionized, thereby increasing the nucleophilicity (reactivity). The alkali compound contained in the alkali solution is not particularly limited, and may be an inorganic alkali compound or an organic alkali compound. For example, sodium hydroxide, potassium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide are preferably used because of their high versatility. The alkali cellulose may be made into an alkali cellulose simultaneously with the introduction of an ionic substituent, before the introduction, or at both the same timing.
[0079] The solution temperature at the start of alkali cellulose formation is preferably 0°C or higher and 50°C or lower, more preferably 5°C or higher and 40°C or lower, and even more preferably 10°C or higher and 30°C or lower.
[0080] The alkali concentration in the alkali solution is preferably 0.01 mol / L to 4 mol / L in terms of molar concentration, more preferably 0.1 mol / L to 3 mol / L inclusive, and even more preferably 1 mol / L to 2.5 mol / L inclusive. In particular, when the treatment temperature in the alkali cellulose formation is less than 10° C., the alkali concentration is preferably 1 mol / L to 2 mol / L inclusive.
[0081] The treatment time for alkali cellulose formation is preferably 1 minute or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more, and the alkali treatment time is preferably 6 hours or less, more preferably 5 hours or less, and even more preferably 4 hours or less.
[0082] By adjusting the type of alkaline solution, treatment temperature, concentration, and immersion time as described above, it is possible to suppress the penetration of the alkaline solution into the crystalline regions of cellulose, making it easier to maintain the crystal structure of cellulose type I, and increasing the yield of fine fibrous cellulose.
[0083] When the introduction of ionic substituents and the conversion to alkali cellulose are not carried out simultaneously, the conversion to alkali cellulose is preferably carried out before the introduction of ionic substituents. In this case, the alkali cellulose obtained by the conversion to alkali cellulose is preferably subjected to solid-liquid separation and water removal by a general deliquation method such as centrifugation or filtration. This improves the reaction efficiency in the subsequent ionic substituent introduction step. The cellulose fiber concentration after solid-liquid separation is preferably 5% to 50%, more preferably 10% to 40%, and even more preferably 15% to 35%.
[0084] -Phosphonic or phosphine group introduction step (phosphoalkylation step)- The ionic substituent introduction step may include a phosphonic or phosphine group introduction step (phosphoalkylation step). In the phosphoalkylation step, a compound having a reactive group and a phosphonic or phosphine group (compound E A ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a phosphonic or phosphine group into the fiber raw material.
[0085] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E A Examples of the compound include vinyl phosphonic acid, phenyl vinyl phosphonic acid, and phenyl vinyl phosphinic acid. From the viewpoints of the efficiency of introducing the substituent, the defibration efficiency, the cost, and the ease of handling, compound E A is preferably vinylphosphonic acid. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0086] Compound E A When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0087] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0088] Compound E A The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0089] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0090] -Sulfonic group introduction step (sulfoalkylation step)- The ionic substituent introduction step may include a sulfone group introduction step (sulfoalkylation step). In the sulfoalkylation, a compound having a reactive group and a sulfone group (compound E) is used as an essential component. B ) and, as an optional component, an alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a sulfone group into the fiber raw material.
[0091] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E B Examples of suitable sulfonates include sodium 2-chloroethanesulfonate, sodium vinylsulfonate, sodium p-styrenesulfonate, and 2-acrylamido-2-methylpropanesulfonic acid. Among these, compound E is particularly preferred in terms of the efficiency of introducing substituents, and therefore the defibration efficiency, cost, and ease of handling. B is preferably sodium vinyl sulfonate. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0092] Compound E B When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0093] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0094] Compound E BThe amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0095] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 15 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0096] -Carboxyalkylation step (third carboxy group introduction step)- The ionic substituent introduction step may include a carboxyalkylation step. As an essential component, a compound having a reactive group and a carboxy group (compound E C ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a carboxyl group into the fiber raw material.
[0097] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Compound E C As the chloropropionic acid, monochloroacetic acid, sodium monochloroacetate, 2-chloropropionic acid, 3-chloropropionic acid, sodium 2-chloropropionate, and sodium 3-chloropropionate are preferred from the standpoint of efficiency of introducing substituents, and therefore defibration efficiency, cost, and ease of handling. Furthermore, as an optional component, it is also preferable to use compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and the amount added is also preferably as described above.
[0098] Compound E CWhen adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0099] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0100] Compound E C The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0101] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1,000 minutes, more preferably from 3 minutes to 500 minutes, and even more preferably from 5 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0102] -Cationic group introduction step (cationization step)- As an essential component, a compound having a reactive group and a cationic group (compound E D ), an optional alkaline compound, and compound B selected from the above-mentioned urea and its derivatives are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a cationic group into the fiber raw material.
[0103] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group). Examples of the cationic group include an ammonium group, a phosphonium group, a sulfonium group, etc. Among these, the cationic group is preferably an ammonium group. Compound E D As the alkyl group, glycidyl trimethyl ammonium chloride, 3-chloro-2-hydroxypropyl trimethyl ammonium chloride, etc. are preferred from the viewpoints of the efficiency of introducing a substituent, and therefore the defibration efficiency, cost, and ease of handling. Furthermore, as an optional component, it is also preferable to use the compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner. The amount of addition is also preferably as described above.
[0104] Compound E D When adding, it may be added to the fiber raw material as a reagent (solid or liquid) as it is, or may be dissolved in a suitable solvent and added. It is preferable that the fiber raw material is converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0105] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0106] Compound E D The amount of addition per 100 parts by mass of the fiber raw material is preferably 1 part by mass or more and 100,000 parts by mass or less, more preferably 2 parts by mass or more and 10,000 parts by mass or less, and even more preferably 5 parts by mass or more and 1,000 parts by mass or less.
[0107] The reaction time may vary depending on the reaction temperature, but is preferably from 1 minute to 1,000 minutes, more preferably from 5 minutes to 500 minutes, and even more preferably from 10 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0108] (Cleaning process) In the method for producing fine fibrous cellulose in this embodiment, a washing step can be carried out on the ionic substituent-introduced fiber as necessary. The washing step is carried out, for example, by washing the ionic substituent-introduced fiber with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.
[0109] (Alkaline treatment (neutralization) process) When producing fine fibrous cellulose, an alkali treatment (neutralization treatment) may be performed on the fiber raw material between the ionic substituent introduction step and the defibration treatment step described below. The alkali treatment method is not particularly limited, but may be, for example, a method of immersing the ionic substituent-introduced fiber in an alkali solution. The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility. The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, from 5° C. to 80° C., and more preferably from 10° C. to 60° C. The time for immersing the ionic substituent-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is, for example, preferably from 5 minutes to 30 minutes, and more preferably from 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the bone dry mass of the ionic substituent-introduced fiber.
[0110] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the ionic substituent-introduced fiber may be washed with water or an organic solvent after the ionic substituent-introducing step and before the alkaline treatment step. From the viewpoint of improving handleability, it is preferable to wash the alkaline-treated ionic substituent-introduced fiber with water or an organic solvent after the alkaline treatment step and before the defibration treatment step.
[0111] (Acid treatment process) When producing fine fibrous cellulose, the fiber raw material may be subjected to an acid treatment between the step of introducing an ionic substituent and the defibration treatment step described below. For example, the steps of introducing an ionic substituent, the acid treatment, the alkali treatment, and the defibration treatment may be performed in this order. The method of acid treatment is not particularly limited, but may be, for example, a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, but is preferably, for example, 10% by mass or less, and more preferably, 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably, for example, 0 to 4, and more preferably, 1 to 3. The acid contained in the acidic solution may be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, or the like. Examples of inorganic acids include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid. The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably, for example, from 5° C. to 100° C., and more preferably from 20° C. to 90° C. The immersion time in the acid solution in the acid treatment is not particularly limited, but is, for example, preferably from 5 minutes to 120 minutes, and more preferably from 10 minutes to 60 minutes. The amount of the acid solution used in the acid treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the bone dry mass of the fiber raw material.
[0112] (Fibrillation process) By subjecting the ionic substituent-introduced fibers to a defibration treatment in a defibration treatment step, fine fibrous cellulose can be obtained. In the defibration process, for example, a defibration treatment device can be used. The defibration treatment device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer, an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration treatment devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.
[0113] In the defibration process, for example, it is preferable to dilute the ionic substituent-introduced fiber with a dispersion medium to make it into a slurry state. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. As the alcohols, for example, methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. are mentioned. As the polyhydric alcohols, for example, ethylene glycol, propylene glycol, glycerin, etc. are mentioned. As the ketones, acetone, methyl ethyl ketone (MEK), etc. are mentioned. As the ethers, for example, diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. are mentioned. As the esters, for example, ethyl acetate, butyl acetate, etc. are mentioned. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0114] The solids concentration of the fine fibrous cellulose during the defibration treatment can be appropriately set. Furthermore, the slurry obtained by dispersing the phosphorus oxo acid group-introduced fiber in a dispersion medium may contain solid matters other than the phosphorus oxo acid group-introduced fiber, such as urea having hydrogen bonding properties.
[0115] (Nitrogen removal treatment) The process for producing fine fibrous cellulose may further include a step of reducing the amount of nitrogen (nitrogen removal process). By reducing the amount of nitrogen, fine fibrous cellulose that can be further suppressed from being discolored can be obtained. The nitrogen removal process is preferably carried out before the defibration process.
[0116] In the nitrogen removal treatment step, it is preferable to adjust the pH of the slurry containing the substituent-introduced fiber to 10 or more and perform a heat treatment. In the heat treatment, the liquid temperature of the slurry is preferably 50° C. or more and 100° C. or less, and the heating time is preferably 15 minutes or more and 180 minutes or less. When adjusting the pH of the slurry containing the substituent-introduced fiber, it is preferable to add an alkali compound that can be used in the above-mentioned alkali treatment step to the slurry.
[0117] After the nitrogen removal treatment step, the fiber having ionic substituents introduced therein may be subjected to a washing step, if necessary. The washing step is carried out, for example, by washing the fiber having ionic substituents introduced therein with water or an organic solvent. The number of washing steps carried out in each washing step is not particularly limited.
[0118] (Substituent removal treatment) The method for producing fine fibrous cellulose may include a step of removing at least a part of the substituent from fine fibrous cellulose having a substituent and a fiber width of 1 nm to 1000 nm. By passing through such a step, it is possible to obtain fine fibrous cellulose having a small amount of substituents introduced but a small fiber width. In this specification, the step of removing at least a part of the substituent from the fine fibrous cellulose is also referred to as a substituent removal treatment step.
[0119] Examples of the substituent removal treatment step include a step of heat treating, enzyme treating, acid treating, alkali treating, etc., fine fibrous cellulose having a substituent and a fiber width of 1 nm to 1000 nm. These may be performed alone or in combination. Among them, the substituent removal treatment step is preferably a heat treating step or an enzyme treating step. By going through the above treatment steps, at least a part of the substituent is removed from the fine fibrous cellulose having a substituent and a fiber width of 1 nm to 1000 nm, and a fine fibrous cellulose having an introduction amount of less than 0.5 mmol / g can be obtained. By forming a fine fibrous cellulose-containing layer using such fine fibrous cellulose, a laminate having better water resistance can be obtained.
[0120] The substituent removal treatment step is preferably carried out in the form of a slurry. That is, the substituent removal treatment step is preferably a step of heating, enzymatically treating, acid-treating, alkali-treating, or the like, a slurry containing a fine fibrous cellulose having a substituent and a fiber width of 1 nm to 1000 nm. By carrying out the substituent removal treatment step in the form of a slurry, it is possible to prevent the residue of colored substances generated by heating or the like during the substituent removal treatment, and added or generated acids, alkalis, salts, and the like. This makes it possible to suppress coloring of the fine fibrous cellulose-containing layer. In addition, when performing a treatment to remove salts derived from the substituents removed after the substituent removal treatment, it is also possible to increase the efficiency of salt removal.
[0121] When a substitution removal treatment is performed on a slurry containing fine fibrous cellulose having a substituent and a fiber width of 1 nm to 1000 nm, the concentration of the fine fibrous cellulose in the slurry is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more. In addition, the concentration of the fine fibrous cellulose in the slurry is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less. By setting the concentration of the fine fibrous cellulose in the slurry within the above range, the substitution removal treatment can be performed more efficiently. Furthermore, by setting the concentration of the fine fibrous cellulose in the slurry within the above range, it is possible to prevent the coloring substances generated by heating during the substitution removal treatment, and the residue of acids, alkalis, salts, etc. that are added or generated. This makes it possible to suppress the coloring of the fine fibrous cellulose-containing layer. In addition, when performing a treatment to remove salts derived from the substituents removed after the substitution removal treatment, it is also possible to increase the efficiency of removing the salts.
[0122] When the substituent removal treatment step is a step of heat treating fine fibrous cellulose having a substituent and a fiber width of 1 nm or more and 1000 nm or less, the heating temperature in the heat treatment step is preferably 40° C. or more, more preferably 50° C. or more, and even more preferably 60° C. or more. The heating temperature in the heat treatment step is preferably 250° C. or less, more preferably 230° C. or less, and even more preferably 200° C. or less. In particular, when the substituent of the fine fibrous cellulose to be subjected to the substituent removal treatment step is a phosphorus oxo acid group, the heating temperature in the heat treatment step is preferably 80° C. or more, more preferably 100° C. or more, and even more preferably 120° C. or more.
[0123] When the substituent removal treatment step is a step of heat treatment, the heating device that can be used in the heat treatment step is not particularly limited, but a hot air heating device, a steam heating device, an electric heating device, a hydrothermal heating device, a thermal heating device, an infrared heating device, a far-infrared heating device, a microwave heating device, a high-frequency heating device, a stirring dryer, a rotary dryer, a disk dryer, a roll-type heating device, a plate-type heating device, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, and a reduced pressure dryer can be used. From the viewpoint of preventing evaporation, it is preferable that the heating is performed in a closed system, and from the viewpoint of further increasing the heating temperature, it is preferable that the heating is performed in a pressure-resistant device or container. The heating treatment may be a batch treatment, a batch continuous treatment, or a continuous treatment.
[0124] When the substituent removal treatment step is a step of enzymatically treating fine fibrous cellulose having substituents and a fiber width of 1 nm or more and 1000 nm or less, it is preferable to use a phosphate ester hydrolase, a sulfate ester hydrolase, or the like in the enzymatic treatment step depending on the type of substituent.
[0125] In the enzyme treatment step, the enzyme is preferably added so that the enzyme activity is 0.1 nkat or more per 1 g of fine fibrous cellulose, more preferably 1.0 nkat or more, and even more preferably 10 nkat or more. The enzyme is preferably added so that the enzyme activity is 100,000 nkat or less per 1 g of fine fibrous cellulose, more preferably 50,000 nkat or less, and even more preferably 10,000 nkat or less. After adding the enzyme to the fine fibrous cellulose dispersion (slurry), it is preferable to perform a treatment under conditions of 0°C or more and less than 50°C for 1 minute to 100 hours.
[0126] After the enzyme reaction, a step of inactivating the enzyme may be performed. Examples of the method of inactivating the enzyme include a method of inactivating the enzyme by adding an acid component or an alkali component to the slurry that has been subjected to the enzyme treatment, and a method of inactivating the enzyme by raising the temperature of the slurry that has been subjected to the enzyme treatment to 90° C. or higher.
[0127] When the substituent removal treatment step is a step of acid-treating fine fibrous cellulose having a substituent and a fiber width of 1 nm or more and 1000 nm or less, it is preferable to add an acid compound that can be used in the acid treatment step described above to the slurry in the acid treatment step.
[0128] When the substituent removal treatment step is a step of subjecting fine fibrous cellulose having a substituent and having a fiber width of 1 nm or more and 1000 nm or less to an alkali treatment, it is preferable to add an alkali compound that can be used in the above-mentioned alkali treatment step to the slurry in the alkali treatment step.
[0129] In the substituent removal treatment step, it is preferable that the substituent removal reaction proceeds uniformly. In order to proceed with the reaction uniformly, for example, the slurry containing the fine fibrous cellulose may be stirred, or the specific surface area of the slurry may be increased. As a method for stirring the slurry, an external mechanical shear may be applied, or the self-stirring may be promoted by increasing the liquid feed rate of the slurry during the reaction.
[0130] In the substituent removal treatment step, a spacer molecule may be added. The spacer molecule enters between adjacent fine fibrous cellulose particles, thereby acting as a spacer for providing a fine space between the fine fibrous cellulose particles. By adding such a spacer molecule in the substituent removal treatment step, the aggregation of the fine fibrous cellulose particles after the substituent removal treatment can be suppressed. This makes it possible to more effectively increase the transparency of the fine fibrous cellulose-containing layer.
[0131] The spacer molecule is preferably a water-soluble organic compound. Examples of the water-soluble organic compound include sugar, water-soluble polymer, and urea. Specific examples include trehalose, urea, polyethylene glycol (PEG), polyethylene oxide (PEO), carboxymethyl cellulose, and polyvinyl alcohol (PVA). In addition, water-soluble organic compounds that can be used include alkyl methacrylate-acrylic acid copolymers, polyvinylpyrrolidone, sodium polyacrylate, propylene glycol, dipropylene glycol, polypropylene glycol, isoprene glycol, hexylene glycol, 1,3-butylene glycol, polyacrylamide, xanthan gum, guar gum, tamarind gum, carrageenan, locust bean gum, quince seed, alginic acid, pullulan, carrageenan, pectin, cationic starch, raw starch, oxidized starch, etherified starch, esterified starch, amylose and other starches, glycerin, diglycerin, polyglycerin, hyaluronic acid, and metal salts of hyaluronic acid.
[0132] Also, known pigments can be used as spacer molecules, such as kaolin (containing clay), calcium carbonate, titanium oxide, zinc oxide, amorphous silica (containing colloidal silica), aluminum oxide, zeolite, sepiolite, smectite, synthetic smectite, magnesium silicate, magnesium carbonate, magnesium oxide, diatomaceous earth, styrene-based plastic pigments, hydrotalcite, urea resin-based plastic pigments, and benzoguanamine-based plastic pigments.
[0133] (pH adjustment process) When the above-mentioned substituent removal treatment step is carried out in the form of a slurry, a step of adjusting the pH of the slurry containing the fine fibrous cellulose may be provided before the substituent removal treatment step. For example, an ionic substituent is introduced into the cellulose fiber, and the counter ion of the ionic substituent is Na + In this case, the slurry containing the defibrated fine fibrous cellulose exhibits weak alkalinity. If heating is performed in this state, monosaccharides, which are one of the causes of coloring, may be generated due to decomposition of the cellulose, so it is preferable to adjust the pH of the slurry to 8 or less. Similarly, monosaccharides may be generated under acidic conditions, so it is preferable to adjust the pH of the slurry to 3 or more.
[0134] In addition, when the fine fibrous cellulose having a substituent is a fine fibrous cellulose having a phosphate group, from the viewpoint of improving the efficiency of removing the substituent, it is preferable that the phosphorus of the phosphate group is in a state that is easily susceptible to nucleophilic attack. The phosphorus that is easily susceptible to nucleophilic attack is cellulose-OP(=O)(-OH + )(-O-Na + ) is a state of neutralization level 1, and to achieve this state, The pH of the slurry is preferably adjusted to 3 or more and 8 or less, and more preferably adjusted to 4 or more and 6 or less.
[0135] The means for adjusting the pH is not particularly limited, and for example, an acid component or an alkali component may be added to the slurry containing the fine fibrous cellulose. The acid component may be either an inorganic acid or an organic acid, and examples of the inorganic acid include sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid. Examples of the organic acid include formic acid, acetic acid, citric acid, malic acid, lactic acid, adipic acid, sebacic acid, stearic acid, maleic acid, succinic acid, tartaric acid, fumaric acid, and gluconic acid. The alkali component may be an inorganic alkali compound or an organic alkali compound. Examples of the inorganic alkali compound include lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, lithium hydrogen carbonate, potassium carbonate, potassium hydrogen carbonate, sodium carbonate, and sodium hydrogen carbonate. Examples of the organic alkali compound include ammonia, hydrazine, methylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, diaminoethane, diaminopropane, diaminobutane, diaminopentane, diaminohexane, cyclohexylamine, aniline, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, pyridine, and N,N-dimethyl-4-aminopyridine.
[0136] In addition, in the pH adjustment step, an ion exchange treatment may be performed to adjust the pH. In the ion exchange treatment, a strong acid cation exchange resin or a weak acid ion exchange resin may be used. By treating with an appropriate amount of cation exchange resin for a sufficient time, a slurry containing fine fibrous cellulose with a desired pH can be obtained. Furthermore, in the pH adjustment step, the addition of an acid component or an alkali component may be combined with the ion exchange treatment.
[0137] (Salt removal process) After the substituent removal treatment step, it is preferable to carry out a treatment for removing salts derived from the removed substituents. By removing the salts derived from the substituents, it becomes easier to obtain fine fibrous cellulose capable of suppressing coloration. The means for removing the salts derived from the substituents is not particularly limited, and examples thereof include a washing treatment and an ion exchange treatment. The washing treatment is carried out by washing the fine fibrous cellulose aggregated in the substituent removal treatment with, for example, water or an organic solvent. In the ion exchange treatment, an ion exchange resin can be used.
[0138] (Uniform dispersion processing) The substituent removal treatment step may be followed by a step of uniformly dispersing the fine fibrous cellulose obtained through the substituent removal treatment. By subjecting the fine fibrous cellulose to the substituent removal treatment, at least a portion of the fine fibrous cellulose is aggregated. The uniform dispersion treatment step is a step of uniformly dispersing the fine fibrous cellulose thus aggregated.
[0139] In the uniform dispersion treatment step, for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a twin-shaft kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser or a beater can be used. Among the above uniform dispersion treatment devices, it is more preferable to use a high-speed defibrator or a high-pressure homogenizer.
[0140] The treatment conditions in the uniform dispersion treatment step are not particularly limited, but it is preferable to increase the maximum movement speed of the fine fibrous cellulose during treatment and the pressure during treatment. In the case of a high-speed defibrator, the peripheral speed is preferably 20 m / sec or more, more preferably 25 m / sec or more, and even more preferably 30 m / sec or more. A high-pressure homogenizer is more preferably used because it has a higher maximum movement speed of the fine fibrous cellulose during treatment and a higher pressure during treatment than a high-speed defibrator. In the high-pressure homogenizer treatment, the pressure during treatment is preferably 1 MPa or more and 350 MPa or less, more preferably 10 MPa or more and 300 MPa or less, and even more preferably 50 MPa or more and 250 MPa or less.
[0141] In the uniform dispersion treatment step, the above-mentioned spacer molecules may be added. By adding such spacer molecules in the uniform dispersion treatment step, the fine fibrous cellulose can be uniformly dispersed more smoothly. This makes it possible to more effectively increase the transparency of the fine fibrous cellulose-containing layer.
[0142] As the fine fibrous cellulose, a fine fibrous cellulose containing an ionic group and an unmodified fine fibrous cellulose may be used in combination.
[0143] (fibrous cellulose with a fiber width of over 1,000 nm) The coating liquid for forming a fiber layer may contain fibrous cellulose having a fiber width of more than 1,000 nm. Hereinafter, fibrous cellulose having a fiber width of more than 1,000 nm is also referred to as "coarse cellulose fiber." The upper limit of the fiber width of the coarse cellulose is, for example, 30,000 nm or less, preferably 20,000 nm or less.
[0144] (dispersion medium) The fiber layer forming coating liquid preferably contains a dispersion medium in order to form a fiber layer in which fine fibrous cellulose is uniformly dispersed. The dispersion medium is preferably one containing water as a main component, and may contain an organic solvent in addition to water. Examples of the organic solvent include the polar organic solvents listed in the fiber defibration process. The water content in the solvent of the fiber layer forming coating liquid is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, still more preferably 95% by mass or more, and 100% by mass or less, with 100% by mass being preferred.
[0145] (Other ingredients 2) The fiber layer forming coating liquid may contain components other than the hydrophilic polymer, the fine fibrous cellulose having a fiber width of 1 nm to 1,000 nm, and the coarse cellulose ("other components 2"). Examples of other components 2 include hydrophilic low molecular weight, thermoplastic resins, surfactants, organic ions, coupling agents, inorganic layered compounds, inorganic compounds, leveling agents, preservatives, defoamers, organic particles, lubricants, antistatic agents, UV protection agents, dyes, pigments, stabilizers, magnetic powders, alignment promoters, plasticizers, dispersants, color inhibitors, polymerization inhibitors, pH adjusters, and crosslinking agents.
[0146] (Content) From the viewpoint of improving the interlayer adhesion between the fiber layer and the resin layer, the content of the hydrophilic polymer in the solid content of the coating liquid for forming the fiber layer is preferably 5 mass% or more, more preferably 15 mass% or more, even more preferably 25 mass% or more, and is preferably 55 mass% or less, more preferably 45 mass% or less, even more preferably 35 mass% or less.
[0147] In terms of enhancing the function as a reinforcing material for the laminate sheet, the content of fine fibrous cellulose in the solid content of the coating liquid for forming a fiber layer is preferably 45 mass% or more, more preferably 50 mass% or more, even more preferably 55 mass% or more, even more preferably 60 mass% or more, particularly preferably 65 mass% or more, and is preferably 95 mass% or less, more preferably 90 mass% or less, even more preferably 85 mass% or less, even more preferably 80 mass% or less, particularly preferably 75 mass% or less. From the viewpoint of improving the interlayer adhesion between the fiber layer and the resin layer, the content of coarse cellulose fibers in the solid content of the coating liquid for forming a fiber layer is preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 20 mass% or less, still more preferably 5 mass% or less, and particularly preferably 0 mass%. The content of other component 2 in the solid content of the coating liquid for forming a fiber layer can be, for example, 5 mass% or less, or may be 3 mass% or less, or may be 1 mass% or less, or may be 0 mass%.
[0148] (concentration) From the viewpoint of forming a fiber layer in which the solids in the coating liquid are uniformly dispersed, and from the viewpoint of coatability, the solids concentration in the coating liquid for forming a fiber layer is preferably 0.05 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, still more preferably 1.0 mass% or more, and is preferably 10 mass% or less, more preferably 8.0 mass% or less, even more preferably 5.0 mass% or less, and still more preferably 3.0 mass% or less.
[0149] (Coating and drying) The fiber layer forming coating liquid can be applied onto the resin layer (1a) using a known coating machine. Examples of the coating machine that can be used include a bar coater, a roll coater, a gravure coater, a die coater, a curtain coater, and an air doctor coater. A bar coater, a die coater, a curtain coater, and a spray coater are preferred because they can achieve a more uniform thickness. The temperature of the coating liquid for forming a fiber layer is not particularly limited, but is preferably from 15° C. to 45° C. When the coating temperature is equal to or higher than the lower limit, the fine fibrous cellulose dispersion can be easily coated, and when the coating temperature is equal to or lower than the upper limit, evaporation of the solvent during coating can be suppressed.
[0150] In the case where the viscosity of the coating liquid for forming the fiber layer is low and the coating liquid spreads on the resin layer (1a) during coating, a frame for blocking may be fixed on the resin layer (1a) to obtain a fiber layer of the desired thickness and basis weight. The material of the frame for blocking is not particularly limited, but it is preferable to select a material that allows the end of the fiber layer to be easily peeled off after drying. Among them, a molded resin plate or a metal plate is preferable, but is not particularly limited. For example, resin plates such as acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, and polyvinylidene chloride plates, metal plates such as aluminum plates, zinc plates, copper plates, and iron plates, and metal plates whose surfaces have been oxidized, stainless steel plates, brass plates, and the like can be used.
[0151] The lower limit of the drying temperature is not limited as long as the fiber layer can be formed at a temperature lower than the dissociation temperature of the blocking agent of the blocked isocyanate compound in the resin layer (1a), and is preferably at least 70° C., more preferably at least 75° C., and is preferably at most 100° C., more preferably at most 95° C. The drying time is preferably at least 4 minutes, more preferably at least 7 minutes, and is preferably at most 13 minutes, more preferably at most 16 minutes. The drying method in step 2 is the same as the drying method in step 1. In step 2, the coating and drying steps can be repeated to obtain a fiber layer of a desired thickness.
[0152] [Step 3] Step 3 is a step of heating the sheet on which the fiber layer is formed to form a resin layer (1A), and the heating temperature is equal to or higher than the dissociation temperature of the blocking agent of the blocked isocyanate compound contained in the resin layer (1a). In step 3, the blocking agent is dissociated from the blocked isocyanate compound, and the isocyanate compound is reacted with the resin contained in the resin layer (1a), the resin contained in the fiber layer, and the fine fibrous cellulose to form the resin layer (1A). The heating temperature is preferably 110° C. or higher, more preferably 115° C. or higher, and preferably 130° C. or lower, more preferably 125° C. or lower. The heating time is preferably 30 minutes or longer, more preferably 60 minutes or longer, and preferably 180 minutes or shorter, more preferably 150 minutes or shorter. The heating in step 3 can be carried out in the same manner as the drying method in step 1.
[0153] The method for producing the laminate sheet of the present embodiment may further include the following step 4. [Step 4] Step 4 is a step of forming a resin layer (2a) by applying a coating liquid for forming a resin layer (2A) containing a resin and at least one compound selected from the group consisting of an isocyanate compound and a blocked isocyanate compound to the surface of the fiber layer opposite to the resin layer (1A), and drying the coating liquid. In step 5 described below, the resin layer (2a) is turned into a resin layer (2A), and the resin layer (2A) is further bonded to a resin plate to obtain a laminate.
[0154] <Coating liquid for forming resin layer (2A)> The coating liquid for forming the resin layer (2A) contains a resin and at least one selected from the group consisting of an isocyanate compound and a blocked isocyanate compound. From the viewpoint of improving the transparency of the laminate sheet, the coating liquid for forming the resin layer (2A) preferably contains an isocyanate compound.
[0155] (resin) The resin contained in the coating liquid for forming the resin layer (2A) is the same as the resin contained in the coating liquid for forming the resin layer (1A).
[0156] (Isocyanate compounds) The isocyanate compound is a polyisocyanate compound having two or more (preferably 2 to 4, more preferably 2 or 3) isocyanate groups, and examples thereof include aromatic polyisocyanates having 6 to 20 carbon atoms, aliphatic polyisocyanates having 2 to 18 carbon atoms, alicyclic polyisocyanates having 6 to 15 carbon atoms, aralkyl polyisocyanates having 8 to 15 carbon atoms, modified products of these polyisocyanates, and mixtures of two or more of these. Among these, alicyclic polyisocyanates having 6 to 15 carbon atoms, i.e., isocyanurates, are preferred. The carbons of the above carbon numbers do not include the carbons of the isocyanato groups.
[0157] Specific examples of aromatic polyisocyanates having 6 or more and 20 or less carbon atoms include tolylene diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, and 4,4'-diphenyl ether diisocyanate.
[0158] Specific examples of alicyclic polyisocyanates having 6 to 15 carbon atoms include isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, and 2,6-norbornane diisocyanate.
[0159] Specific examples of aliphatic polyisocyanates having 2 to 18 carbon atoms include ethylene diisocyanate, trimethylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and 2,6-diisocyanate methylcaproate.
[0160] Specific examples of aralkyl polyisocyanates having 8 to 15 carbon atoms include xylylene diisocyanate, tetramethylxylylene diisocyanate, and ω,ω'-diisocyanate-1,4-diethylbenzene.
[0161] The content of isocyanato groups in the isocyanate compound is preferably 0.5 mmol / g or more, more preferably 0.6 mmol / g or more, even more preferably 0.8 mmol / g or more, and particularly preferably 0.9 mmol / g or more, and the content of isocyanato groups is preferably 3.0 mmol / g or less, more preferably 2.5 mmol / g or less, even more preferably 2.0 mmol / g or less, and particularly preferably 1.5 mmol / g or less.
[0162] The isocyanate compound may be a commercially available product, for example, Takenate D101-E (manufactured by Mitsui Chemicals, Inc.), Duranate TPA-100 (Asahi Kasei Corporation), Duranate MFA-75B (Asahi Kasei Corporation), and Coronate L55-E (Tosoh Corporation).
[0163] (Blocked isocyanate compound) The blocked isocyanate compound contained in the coating liquid for forming the resin layer (2A) is the same as the blocked isocyanate compound contained in the coating liquid for forming the resin layer (1A).
[0164] (Organic solvent) From the viewpoint of ease of formation of the resin layer (2a), the coating liquid for forming the resin layer (2A) preferably contains an organic solvent, and the organic solvent is the same as the organic solvent in the coating liquid for forming the resin layer (1A).
[0165] (Other Ingredients 3) The coating liquid for forming the resin layer (2A) may contain components other than the above-mentioned resin, isocyanate compound, blocked isocyanate compound, and organic solvent ("other components 3"). The other components 3 are the same as the other components 1 of the coating liquid for forming the resin layer (1A).
[0166] (Content) The solid content of the coating liquid for forming the resin layer (2A) is, from the viewpoints of easiness in forming the resin layer (2a) and improving the interlayer adhesion between the fiber layer and the resin layer, preferably 3 mass % or more, more preferably 6 mass % or more, even more preferably 9 mass % or more, and preferably 30 mass % or less, more preferably 25 mass % or less, even more preferably 20 mass % or less. The resin content in the solid content of the coating liquid for forming the resin layer (2A) is, from the viewpoints of easiness in forming the resin layer (2a) and improving the interlayer adhesion between the fiber layer and the resin layer, preferably 40 mass% or more, more preferably 50 mass% or more, even more preferably 60 mass% or more, and is preferably 90 mass% or less, more preferably 85 mass% or less, even more preferably 80 mass% or less. The total content of the isocyanate compound and the blocked isocyanate compound in the solid content of the coating liquid for forming the resin layer (2A) is, from the viewpoints of easiness in forming the resin layer (2a) and improvement in interlayer adhesion between the fiber layer and the resin layer, preferably 10 mass% or more, more preferably 15 mass% or more, even more preferably 20 mass% or more, and is preferably 50 mass% or less, more preferably 45 mass% or less, even more preferably 40 mass% or less. In the solid content of the coating liquid for forming the resin layer (2A), the total content of the resin, the isocyanate compound and the blocked isocyanate compound is preferably 85 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and is 100 mass% or less, preferably 100 mass%. In the coating liquid for forming the resin layer (2A), the total content of the isocyanate compound and the blocked isocyanate compound relative to 100 parts by mass of the resin is, from the viewpoint of improving the interlayer adhesion between the fiber layer and the resin layer, preferably 10 parts by mass or more, more preferably 15 parts by mass or more, even more preferably 20 parts by mass or more, and is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less. The content of the other component 3 in the solid content of the coating fluid for forming the resin layer (2A) is the same as the content of the other component 1 in the solid content of the coating fluid for forming the resin layer (1A).
[0167] (concentration) The solids concentration in the coating liquid for forming the resin layer (2A) is the same as the solids concentration in the coating liquid for forming the resin layer (1A).
[0168] (Coating and drying) The coating and drying in step 4 is similar to the coating and drying in step 1 except for the drying temperature. The drying temperature in step 4 is preferably 60° C. or higher, more preferably 65° C. or higher, and preferably 95° C. or lower, more preferably 90° C. or lower.
[0169] The method for producing the laminate sheet of the present embodiment may further include the following step 5. [Step 5] Step 5 is a step (aging treatment) of forming a resin layer (2A) by heating the sheet that has been subjected to step 4. By performing step 5, the resin layer (2a) can be made into a resin layer (2A) having a desired adhesiveness. When a blocked isocyanate compound is used in the resin layer (2A), the heating temperature in step 5 is preferably 110° C. or higher, more preferably 115° C. or higher, and preferably 135° C. or lower, more preferably 130° C. or lower, and further preferably 125° C. or lower. The heating time is preferably 30 minutes or longer, more preferably 60 minutes or longer, and preferably 180 minutes or shorter, more preferably 150 minutes or shorter. When an isocyanate compound is used in the resin layer (2A), the heating temperature in step 5 is preferably 80° C. or higher, more preferably 85° C. or higher, and preferably 100° C. or lower, more preferably 95° C. or lower. The heating time is preferably 3 hours or longer, more preferably 5 hours or longer, even more preferably 7 hours or longer, and preferably 14 hours or shorter, more preferably 12 hours or shorter, and even more preferably 10 hours or shorter. The heating temperature and heating time in "when a blocked isocyanate compound is used in the resin layer (2A)" can be combined with the heating temperature and heating time in "when an isocyanate compound is used in the resin layer (2A)" to obtain the heating temperature and heating time in step 5. The heating temperature and heating time in step 5 can be, for example, 80° C. or higher and 135° C. or lower, and 30 minutes or longer and 10 hours or shorter. The heating in step 5 can be carried out in the same manner as the drying method in step 1.
[0170] [Laminated sheet] FIG. 1 is a cross-sectional view illustrating the configuration of a laminate sheet obtained by a method for producing a laminate sheet according to one embodiment of the present invention. The laminate sheet has a resin layer (1A) (2) and a fiber layer (3) in this order on one surface of a thermoplastic resin substrate (1). FIG. 2 is a cross-sectional view illustrating the configuration of a laminate sheet obtained by a method for producing a laminate sheet according to another embodiment of the present invention. The laminate sheet has a resin layer (1A) (2), a fiber layer (3) and a resin layer (2A) (4) in this order on one surface of a thermoplastic resin substrate (1).
[0171] <Thickness> The thickness of the thermoplastic resin substrate is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 50 μm or more, still more preferably 100 μm or more, particularly preferably 150 μm or more, and is preferably 500 μm or less, more preferably 400 μm or less, and even more preferably 320 μm or less. The thickness of the thermoplastic resin substrate is a value measured by cutting out a cross section of the laminated sheet with an ultramicrotome UC-7 (manufactured by JEOL Ltd.) and observing the cross section with an electron microscope, a magnifying glass, or visually. The thickness of the thermoplastic resin substrate is preferably adjusted appropriately depending on the application of the laminate sheet.
[0172] The thickness of the resin layers (1A) and (2A) is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more, and is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. The thickness of the resin layers (1A) and (2A) is a value measured by cutting a cross section of the laminated sheet with an ultramicrotome UC-7 (manufactured by JEOL Ltd.) and observing the cross section with an electron microscope, a magnifying glass or visually. It is preferable that the thickness of the resin layers (1A) and (2A) is appropriately adjusted depending on the application of the laminate sheet.
[0173] The thickness of the fiber layer is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, and is preferably 300 μm or less, more preferably 250 μm or less, and even more preferably 200 μm or less. The thickness of the fiber layer can be measured with a stylus thickness gauge (Millitron 1202D, manufactured by Mahl Co., Ltd.). The thickness of the fiber layer may be measured by cutting out a cross section of the laminated sheet with an ultramicrotome UC-7 (manufactured by JEOL Ltd.) and observing the cross section with an electron microscope, a magnifying glass, or visually. By setting the thickness of the fiber layer in the laminated sheet within the above range, the laminated sheet can exert a stronger reinforcing effect. For example, when the laminated sheet is attached to an adherend such as a resin plate, the strength of the adherend can be reinforced. The thickness of the fiber layer is preferably adjusted appropriately depending on the application of the laminate sheet.
[0174] The thickness of the laminate sheet is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more, and is preferably 1000 μm or less, more preferably 800 μm or less, and even more preferably 600 μm or less. The thickness of the thermoplastic resin substrate is a value measured by cutting out a cross section of the laminate sheet with an ultramicrotome UC-7 (manufactured by JEOL Ltd.) and observing the cross section with an electron microscope, a magnifying glass, or visually. The thickness of the laminate sheet is preferably adjusted appropriately depending on the application of the laminate sheet.
[0175] <density> The density of the fiber layer is 1.0 g / cm 3 It is preferable that the content is 1.2 g / cm or more. 3 More preferably, it is 1.4 g / cm or more. 3 It is more preferable that the density of the fiber layer is 1.7 g / cm or more. 3 It is preferable that the density is 1.6 g / cm or less. 3 It is even more preferable that:
[0176] The density of the fiber layer is calculated from the basis weight and thickness of the fiber layer in accordance with JIS P 8118. The basis weight of the fiber layer can be calculated in accordance with JIS P 8124 by cutting the laminated sheet with an ultramicrotome UC-7 (manufactured by JEOL Ltd.) so that only the fiber layer remains.
[0177] In addition, when the laminated sheet contains two or more fiber layers, the essential components and optional components contained in each fiber layer may be the same or different, and are preferably the same. In addition, the thickness and density of each fiber layer may be the same or different, and are preferably the same. In addition, it is preferable that the thickness and density of the entire fiber layer are within the above range.
[0178] [Haze] The haze of the laminate sheet of this embodiment is preferably 20.0% or less, more preferably 5.0% or less, even more preferably 4.5% or less, and even more preferably 4.0% or less. On the other hand, the lower limit of the haze of the laminate sheet may be, for example, 0%. The haze of the laminate sheet can be controlled by the fiber width of the fine fibrous cellulose, the type of ionic group, the amount of ionic group introduced, the type of resin in the fiber layer, the type of resin constituting the thermoplastic resin substrate, the content of the fine fibrous cellulose and resin in the resin layer, the thickness of each layer constituting the laminate sheet, etc. The haze of the laminate sheet is a value measured in accordance with JIS K7136:2000.
[0179] [Method of manufacturing laminate] The method for producing a laminate of this embodiment includes bonding the resin layer (2A) of the laminate sheet obtained by the method for producing a laminate sheet of this embodiment to a resin plate.
[0180] A resin plate is a plate whose main component is a natural resin or a synthetic resin. Here, the main component refers to a component that is contained in an amount of 50% by mass or more relative to the total mass of the resin plate. The content of the resin component is preferably 60% by mass or more relative to the total mass of the resin plate, more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The content of the resin component may be 100% by mass relative to the total mass of the resin plate.
[0181] Examples of natural resins include rosin-based resins such as rosin, rosin ester, and hydrogenated rosin ester.
[0182] Examples of synthetic resins include polyolefin resins, polycarbonate resins, polyethylene terephthalate resins, polyethylene naphthalate resins, polyimide resins, polystyrene resins, and acrylic resins. Among them, the synthetic resin is preferably a polyolefin resin, and preferably has at least one selected from a polyethylene resin and a polypropylene resin. The polyolefin resin is also preferably a resin having a cyclic olefin structure. In this case, the resin having a cyclic olefin structure may be a cycloolefin resin (COP) or a cycloolefin copolymer.
[0183] The resin layer (2A) of the laminated sheet is preferably bonded to the resin plate by, for example, heat pressing the resin layers (2A) of the two laminated sheets in a state where they are stacked on top of and under the resin plate. The heat pressing conditions can be appropriately selected with reference to the glass transition temperature of the resin plate or the resin layer (2A), etc. The heat pressing conditions are, for example, 1 to 10 MPa, 100 to 200° C., and a holding time of 30 seconds to 5 minutes.
[0184] [Application] The laminate sheet obtained by the method for producing the laminate sheet of this embodiment and the laminate obtained by the method for producing the laminate of this embodiment have excellent interlayer adhesion between the fiber layer and the resin layer, and can reduce haze. The laminate sheet and the laminate are suitable for use as light-transmitting substrates for various display devices, various solar cells, etc. The laminate sheet and the laminate are also suitable for use as substrates for electronic devices, components for home appliances, window materials for various vehicles and buildings, interior materials, exterior materials, packaging materials, etc. EXAMPLES
[0185] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. Unless otherwise specified, the following operations were performed at room temperature (23°C) and a relative humidity of 50% RH.
[0186] <Production Example 1> (Phosphorylation) As the raw pulp, hardwood dissolving pulp (dry sheet) manufactured by Oji Paper Co., Ltd. was used. This raw pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to adjust the composition to 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 250 seconds to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp.
[0187] (Cleaning process) The phosphorylated pulp was then washed. The washing was carried out by pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse it, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.
[0188] (Neutralization treatment) Next, the phosphorylated pulp after washing was subjected to a neutralization treatment as follows. First, the phosphorylated pulp after washing was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain a phosphorylated pulp that had been subjected to a neutralization treatment. Next, the above-mentioned washing treatment was performed on the phosphorylated pulp after the neutralization treatment.
[0189] (Nitrogen removal treatment) Ion-exchanged water was added to the phosphorylated pulp to prepare a slurry with a solid content of 4% by mass. The slurry was adjusted to pH 13.4 by adding 48% by mass of sodium hydroxide aqueous solution, and heated at a liquid temperature of 85°C for 1 hour. The pulp slurry was then dehydrated, and 10 L of ion-exchanged water was poured into 100 g of phosphorylated pulp (bone dry mass) to obtain a pulp dispersion. The pulp was stirred so that the pulp was uniformly dispersed, and the filtration and dehydration were repeated to remove excess sodium hydroxide. The end point of the removal was when the electrical conductivity of the filtrate became 100 μS / cm or less. The amount of carbamide groups introduced, obtained from the amount of nitrogen measured by the measurement method described below, was 0.01 mmol / g.
[0190] The infrared absorption spectrum of the phosphorus oxyoxidized pulp obtained in this way was measured using FT-IR. -1 Absorption due to the P=O of phosphate groups was observed near the 2θ=14° to 17° position, and it was confirmed that phosphate groups had been added to the pulp. In addition, when the obtained phosphorylated pulp was used as a test sample and analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, near 2θ=14° to 17° and near 2θ=22° to 23°, and it was confirmed that cellulose type I crystals were maintained. The amount of phosphate groups (amount of first dissociated acid) measured by the measurement method described below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.
[0191] (Defibrillation process) Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose.
[0192] (Substituent removal treatment (high temperature heat treatment)) The fine fibrous cellulose dispersion was placed in a pressure vessel and heated at 160°C for 15 minutes until the amount of phosphate groups reached 0.08 mmol / g. This operation confirmed the formation of fine fibrous cellulose aggregates.
[0193] (Cleaning of slurry after removing substituents) The slurry after heating was washed by repeatedly adding the same amount of ion-exchanged water as the slurry to make a slurry with a solid content concentration of about 1% by mass, stirring the slurry, and then filtering and dehydrating it. When the electrical conductivity of the filtrate became 10 μS / cm or less, ion-exchanged water was added again to make a slurry with a solid content of about 1% by mass, and the slurry was left to stand for 24 hours. The operation of filtering and dehydrating was further repeated from there, and the washing end point was when the electrical conductivity of the filtrate became 10 μS / cm or less again. Ion-exchanged water was added to the obtained fine fibrous cellulose aggregate, and a slurry was obtained after removing the substituents. The solid content concentration of this slurry was 1.7% by mass.
[0194] (Uniform dispersion of slurry after removing substituents) Ion-exchanged water was added to the obtained slurry after the removal of substituents to make the slurry have a solid content of 1.0% by mass, and the slurry was treated three times at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a dispersion of the substituent-removed fine fibrous cellulose containing the substituent-removed fine fibrous cellulose. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 2 to 4 nm.
[0195] (Measurement of phosphorus oxoacid group content) The amount of phosphorus oxo acid groups (equal to the amount of phosphorus oxo acid groups in phosphorus oxoxidized (phosphorylated or subphosphorylated) pulp) was measured by adding ion-exchanged water to a fine fibrous cellulose dispersion containing the target fine fibrous cellulose to prepare a slurry containing 0.2 mass% of fine fibrous cellulose, treating the resulting slurry with an ion-exchange resin, and then titrating it with an alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; manufactured by Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the ion exchange resin from the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution to the slurry containing fine fibrous cellulose after the ion exchange resin treatment at 5-second intervals while measuring the change in the pH value of the slurry. Nitrogen gas was blown into the slurry for 15 minutes before the start of the titration. In this neutralization titration, two points of maximum increment (differential value of pH with respect to the amount of alkali added) were observed on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum increment point obtained after the start of the alkali addition is called the first end point, and the second maximum increment point obtained next is called the second end point (Figure 3). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point divided by the solid content (g) in the slurry to be titrated was defined as the amount of phosphorus oxo acid group (mmol / g). The amount of alkali (mmol) required from the start of titration to the second end point divided by the solid content (g) in the slurry to be titrated was defined as the total amount of dissociated acid (mmol / g). The amount of phosphorus oxoacid groups (amount of phosphorus oxoacid groups introduced) (mmol / g) indicates the amount of substituents per 1 g of fine fibrous cellulose when the counter ion of the phosphorus oxoacid group is a hydrogen ion (H+).
[0196] <Example 1> (Process 1) A modified polycarbonate (manufactured by Mitsubishi Gas Chemical Company, Inc., Iupizeta RX-2136P) was added to toluene at 10% by mass, and a blocked isocyanate compound (manufactured by Mitsui Chemicals, Inc., Takenate XB-G206, dissociation temperature of blocking agent 110°C) was added to toluene at 5.0% by mass, stirred, and dissolved to obtain a coating liquid for forming a resin layer (1A). The coating liquid for forming a resin layer (1A) was applied to a polyethylene terephthalate substrate (thickness 300 μm, manufactured by Toyobo Co., Ltd.) using a gravure coater, and then dried at 80°C for 5 minutes to form a resin layer (1a). The thickness of the resin layer (1a) was 5 μm.
[0197] (Process 2) After mixing 70 parts by mass of fine fibrous cellulose and 30 parts by mass of hydroxypropylmethylcellulose (65SH-1500, manufactured by Shin-Etsu Chemical Co., Ltd.), the mixture was diluted with ion-exchanged water to a solid content of 1.6% and stirred to obtain a coating liquid for forming a fiber layer. The coating liquid for forming a fiber layer was applied onto the resin layer (1a) using an applicator and dried at 80°C for 50 minutes. The coating and drying were repeated until the thickness of the fiber layer reached about 100 μm.
[0198] (Step 3) The sheet having the fiber layer formed thereon obtained through steps 1 and 2 was subjected to an aging treatment at 120° C. for 2 hours to form a resin layer (1A) (thickness: 5 μm).
[0199] (Step 4) In step 1, the resin layer (2A) forming coating liquid prepared in the same manner as the resin layer (1A) forming coating liquid was applied onto the fiber layer and then dried at 70° C. for 5 minutes to form a resin layer (2a). The thickness of the resin layer (2a) was 5 μm.
[0200] (Step 5) The sheet that had been subjected to step 4 was aged at 120° C. for 2 hours to form a resin layer (2A) (thickness: 5 μm), thereby obtaining a laminated sheet (thickness: 410 μm).
[0201] (Preparation of Laminate) Both sides of a 3 mm thick polycarbonate plate (Teijin Limited, Panlite) were sandwiched between two laminated sheets so that the polycarbonate plate and the resin layer (2A) were in contact with each other. Next, these were sandwiched between two 2 mm thick, 200 mm square stainless steel plates. After that, the plate was inserted into a mini test press (Toyo Seiki Kogyo Co., Ltd., MP-WCH) set at room temperature and heated to 160°C over 3 minutes under a press pressure of 5 MPa. After holding the plate in this state for 1 minute, it was cooled to 30°C over 3 minutes. By the above procedure, a laminate (thickness 3820 μm) of a polycarbonate plate and a laminated sheet was obtained.
[0202] <Example 2> (Process 1) A resin layer (1a) was formed in the same manner as in step 1 of Example 1, except that in step 1 of the example, the amount of the blocked isocyanate compound added was 2.6 mass % and a polycarbonate substrate (thickness 300 μm, manufactured by AGC Inc., Carboglass) was used instead of the polyethylene terephthalate substrate.
[0203] (Process 2) A fiber layer was formed in the same manner as in step 2 of Example 1, except that in step 2 of Example 1, coating and drying were repeated until the thickness of the fiber layer reached about 160 μm.
[0204] (Step 3) A resin layer (1A) was formed in the same manner as in step 3 of Example 1.
[0205] (Step 4) A coating liquid for forming a resin layer (2A) was obtained in the same manner as in step 1 of Example 1, except that in step 1 of Example 1, a polyisocyanate (Takenate D101-E, manufactured by Mitsui Chemicals, Inc.) was used in an amount of 2.6 mass% instead of the blocked polyisocyanate. The coating liquid for forming the resin layer (2A) was applied onto the fiber layer and then dried at 70°C for 5 minutes to form a resin layer (2a). The thickness of the resin layer (2a) was 5 μm.
[0206] (Step 5) The sheet that had been subjected to step 4 was aged at 90° C. for 8 hours to form a resin layer (2A) (thickness: 5 μm), thereby obtaining a laminated sheet (thickness: 470 μm).
[0207] (Preparation of Laminate) A laminate (thickness: 3940 μm) was obtained in the same manner as in Example 1, except that the laminate sheet obtained in Example 2 was used instead of the laminate sheet obtained in Example 1.
[0208] <Example 3> A laminate sheet (thickness 470 μm) and a laminate (thickness 3940 μm) were obtained in the same manner as in Example 2, except that a polyethylene terephthalate substrate (thickness 300 μm, manufactured by Toyobo Co., Ltd.) was used instead of the polycarbonate substrate in Example 2.
[0209] <Example 4> A laminate sheet (thickness: 340 μm) and a laminate (thickness: 3680 μm) were obtained in the same manner as in Example 3, except that the thickness of the fiber layer was 30 μm.
[0210] <Example 5> A laminate sheet (thickness: 340 μm) and a laminate (thickness: 3680 μm) were obtained in the same manner as in Example 2, except that the thickness of the fiber layer was 30 μm.
[0211] <Comparative Example 1> A laminate sheet (thickness 470 μm) and a laminate (thickness 3940 μm) were obtained in the same manner as in Example 2, except that in step 1 of Example 2, polyisocyanate (Takenate D101-E, manufactured by Mitsui Chemicals, Inc.) was used instead of the blocked isocyanate compound, and in step 2, a fiber layer forming coating liquid obtained by using polyvinyl alcohol (Z300, manufactured by Kuraray Co., Ltd.) instead of hydroxypropylmethylcellulose was used only in the initial coating and drying, and thereafter, the fiber layer forming coating liquid obtained in step 2 of Example 2 was used.
[0212] <Comparative Example 2> A laminate sheet (thickness: 480 μm) and a laminate (thickness: 3960 μm) were obtained in the same manner as in Comparative Example 1, except that the thickness of the fiber layer was 170 μm.
[0213] <Comparative Example 3> A laminate sheet (thickness 470 μm) and a laminate (thickness 3940 μm) were obtained in the same manner as in Example 2, except that in step 1 of Example 2, a polyisocyanate (Takenate D101-E, manufactured by Mitsui Chemicals, Inc.) was used instead of the blocked isocyanate compound.
[0214] <Comparative Example 4> A laminate sheet (thickness 440 μm) and a laminate (thickness 3880 μm) were obtained in the same manner as in Comparative Example 1, except that a polyethylene terephthalate substrate (thickness 300 μm, manufactured by Toyobo Co., Ltd.) was used instead of the polycarbonate substrate, and the thickness of the fiber layer was 130 μm.
[0215] <Sheet evaluation> (transparency) The haze of the laminated sheet was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) in accordance with JIS K 7136: 2000. The results are shown in Table 1.
[0216] (Interlayer adhesion between fiber layer and resin layer (1A)) Compliant with JIS K 5400, 1mm on the surface of the fiber layer 2 A hundred cross-cuts of the above were placed, cellophane tape (manufactured by Nichiban Co., Ltd.) was attached and pressed on top of them, and then peeled off in a 60° direction. Depending on the presence or absence of peeled masses, the interlayer adhesion between the resin layer (1A) and the fiber layer (sheet containing fine fibrous cellulose) was evaluated according to the following criteria. The results are shown in Table 1. A: The number of peeled squares is 0 points B: The number of peeled squares is 1 or more.
[0217] <Evaluation of the laminate> (Adhesion between resin plate and laminated sheet) The laminate surface was cut with a cutter blade to draw a frame, and the cut end was then turned up with the cutter blade, after which the laminate sheet was peeled off from the resin plate to evaluate the adhesion between the resin plate (a 3 mm thick polycarbonate plate (Panlite, manufactured by Teijin Limited)) and the laminate sheet. The adhesion was evaluated according to the following criteria based on the evaluation results. The results are shown in Table 1. A: The laminated sheet is destroyed or cannot be peeled off. B: The laminated sheet peels off, but resistance is strong. C: The laminated sheet peels off easily.
[0218] [Table 1]
[0219] (Table Notes) BI: blocked isocyanate compound (the number in parentheses is the content of the blocked isocyanate compound relative to 100 parts by mass of polycarbonate in the coating liquid for forming the resin layer (1A)). NI: isocyanate compound (the value in parentheses is the content of the isocyanate compound relative to 100 parts by mass of polycarbonate in the coating liquid for forming the resin layer (1A)). PET: Polyethylene terephthalate PC: Polycarbonate
[0220] As can be seen from the results in Table 1, the laminate sheets obtained by the method for producing a laminate sheet of the present invention had excellent interlayer adhesion between the fiber layer and the resin layer (Examples 1 to 5). In contrast, the laminate sheets produced by using an isocyanate compound instead of a blocked isocyanate compound in step 1 of the laminate sheet production method of the present invention had poor interlayer adhesion between the fiber layer and the resin layer (Comparative Examples 1 to 4). [Explanation of symbols]
[0221] 1 Thermoplastic resin base material 2 Resin layer (1A) 3 Fiber layer 4 Resin layer (2A)
Claims
1. A method for producing a laminate sheet having a resin layer (1A) and a fiber layer in this order on at least one surface of a thermoplastic resin substrate, comprising: The method includes the following steps 1 to 3: Step 1: A step of forming a resin layer (1a) by applying a coating liquid for forming a resin layer (1A) containing a resin and a blocked isocyanate compound to at least one surface of a thermoplastic resin substrate and drying the coating liquid. Step 2: A step of forming a fiber layer by applying a fiber layer-forming coating liquid containing a resin and fine fibrous cellulose having a fiber width of 1 nm or more and 1,000 nm or less to the surface of the resin layer (1a) opposite to the thermoplastic resin substrate, and drying the coating liquid to form a fiber layer. Step 3: A step of heating the sheet on which the fiber layer is formed to form a resin layer (1A) the drying temperatures in steps 1 and 2 are lower than the dissociation temperature of the blocking agent of the blocked isocyanate compound, and the heating temperature in step 3 is equal to or higher than the dissociation temperature of the blocking agent of the blocked isocyanate compound; A method for manufacturing a laminated sheet.
2. The method for producing a laminate sheet according to claim 1, wherein the drying temperature in step 1 is 70°C or higher and 95°C or lower.
3. The method for producing a laminate sheet according to claim 1 or 2, wherein the drying temperature in step 2 is 70°C or higher and 100°C or lower.
4. The method for producing a laminate sheet according to claim 1 or 2, wherein the heating temperature in step 3 is 110°C or higher and 130°C or lower.
5. 3. The method for producing a laminate sheet according to claim 1, wherein the thermoplastic resin constituting the thermoplastic resin substrate comprises at least one selected from the group consisting of polycarbonate and polyethylene terephthalate.
6. The method for producing a laminate sheet according to claim 1 or 2, wherein the coating liquid for forming the resin layer (1A) contains polycarbonate.
7. 3. The method for producing a laminate sheet according to claim 1, wherein the content of the fine fibrous cellulose in the solid content of the fiber layer forming coating liquid is 50% by mass or more.
8. The method for producing a laminate sheet according to claim 1 or 2, further comprising the following step 4: Step 4: A step of forming a resin layer (2a) by applying a coating liquid for forming a resin layer (2A) containing a resin and at least one compound selected from the group consisting of an isocyanate compound and a blocked isocyanate compound to the surface of the fiber layer opposite to the resin layer (1A) and drying the coating liquid.
9. The method for producing a laminate sheet according to claim 8, wherein the drying temperature in step 4 is 60°C or higher and 85°C or lower.
10. The method for producing a laminate sheet according to claim 8, further comprising the following step 5: Step 5: A step of heating the sheet that has been subjected to step 4 to form a resin layer (2A)
11. The method for producing a laminate sheet according to claim 10, wherein the heating temperature in step 5 is 80°C or higher and 135°C or lower.
12. The method for producing a laminate sheet according to claim 8, wherein the coating liquid for forming the resin layer (2A) contains polycarbonate.
13. The method for producing a laminate sheet according to claim 8, wherein the coating liquid for forming the resin layer (2A) contains an isocyanate compound.
14. 3. The method for producing a laminate sheet according to claim 1, wherein the blocked isocyanate compound is a compound obtained by blocking an isocyanato group of hexamethylene diisocyanate.
15. A method for producing a laminate, comprising bonding the resin layer (2A) of the laminate sheet obtained by the method for producing a laminate sheet according to claim 10 to a resin plate.
Citation Information
Patent Citations
Laminated sheet
JP2021181673A
Cited By
Semiconductor device
CN122825492A